Polymer particles and their uses

JP7652352B2Active Publication Date: 2025-03-27SEKISUI PLASTICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022503072
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2020-09-23
Publication Date
2025-03-27
Estimated Expiration
2040-09-23

AI Technical Summary

Benefits of technology

【0012】 本発明の重合体粒子は、重合体粒子、バインダー及び有機溶剤を含む樹脂組成物を形成した際に、樹脂組成物中の分散性及び分散安定性が優れており、また、樹脂組成物中で重合体粒子が均一かつ安定に分散するのに必要な時間が短縮されており、作業性に優れている。 また、樹脂組成物を塗工し塗膜を形成する際においても、重合体粒子の分散性及び分散安定性が維持されることから、塗膜形成時における重合体粒子の過度な凝集を抑制することができる。このため、前記重合体粒子は、フィルム基材上に形成された塗膜全体に重合体粒子が均一に広がり、むらのない安定した光拡散性や防眩性等の光学特性を塗膜に付与できる。 さらに、重合体粒子が含有する界面活性剤の種類(例えば、ポリオキシアルキレン鎖の有無、界面活性剤の溶解度パラメータ(SP値)等)、重合体粒子の単位表面積あたりの界面活性剤の量、及び、重合体粒子の単位表面積あたりの非揮発成分の表面残渣量により、樹脂組成物中での重合体粒子の分散性を調整することが可能である。このため、従来行われていた、重合体粒子の分散性を調整するための重合体粒子のモノマー組成の変更とそれに伴う屈折率調整を行う必要がなくなり、作業性をさらに向上させることができる。 さらに、本発明の重合体粒子は、重合体粒子同士の表面状態の差が小さいことから、樹脂バインダー及び有機溶剤と混合して樹脂組成物を形成した際に、樹脂組成物中での分散均一性に優れるものとなる。また、重合体粒子の表面状態の時間的変化や重合体粒子の製造ロット間での表面状態の差を小さくできることから、品質安定性に優れており、樹脂組成物の製造ロット間での分散状態の差が小さく、分散安定性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652352000001
    Figure 0007652352000001
  • Figure 0007652352000002
    Figure 0007652352000002
  • Figure 0007652352000003
    Figure 0007652352000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing polymer particles which disperse uniformly and stably in a resin composition and in a dry coating film thereof (which have excellent dispersibility and dispersion stability) and for which the required time to disperse uniformly and stably in the resin composition is short. Provided as a means of solving the problem are polymer particles in which: (a) a surfactant that exhibits a solubility parameter (SP value) of 9.0-12.0 and that has a polyoxyalkylene chain is contained in amount per unit surface area of the polymer particles of 1.0×10-3 to 6.0×10-3 g / m2; (b) a surfactant that exhibits a solubility parameter (SP value) of 9.0-12.0 and that does not have polyoxyalkylene chain is contained in an amount per unit surface area of the polymer particles of 5.0×10-5 to 13.0×10-5 g / m2; and (c) the surface residue amount of nonvolatile components per unit surface area of the polymer particles is not more than 2.0×10-3 g / m2.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polymer particles obtained by polymerization reaction and their surfaces modified with a surfactant, and uses thereof. In particular, the present invention relates to polymer particles suitable for use as a raw material for optical components such as light diffusion films and antiglare films, uses of the polymer particles (optical components, paint additives, and antiblocking agents: films and resin molded products containing these), and a method for producing the polymer particles. [Background technology]

[0002] Polymer particles having a volume average particle diameter of 1 to 100 μm are used in applications such as additives for coating agents such as paints (matting agents, etc.), additives for inks (matting agents, etc.), main components or additives for adhesives, additives for artificial marble (shrinkage reducing agents, etc.), paper treatment agents, fillers for external agents such as cosmetics (fillers for improving slipperiness), column fillers used in chromatography, additives for toners used in electrostatic image development, antiblocking agents for films, light diffusing agents for optical members (optical films such as light diffusing films and antiglare films, light diffusers, etc.), and the like.

[0003] Such polymer particles can be produced by polymerizing a polymerizable monomer. As a polymerization method for polymerizing a polymerizable monomer, suspension polymerization, seed polymerization, emulsion polymerization, etc. are known. In these polymerization methods, a surfactant is usually used to stably carry out the polymerization reaction and suppress the generation of coarse particles.

[0004] For example, Patent Document 1 describes polymer particles composed of at least one of a (meth)acrylic polymer, a styrene polymer, and a (meth)acrylic-styrene copolymer. The polymer particles have a particle size variation coefficient of 15.0% or less, and the content of the surfactant having a polyoxyalkylene chain per unit surface area of ​​the polymer particles is 2.0 to 15.0×10 -3 g / m 2 The content of the other surfactant per unit surface area of ​​the polymer particles is 10.0×10-5 g / m 2 The following is the result.

[0005] Patent Document 2 describes polymer particles used as a light diffusing agent, which are obtained by polymerizing a vinyl monomer in a medium containing a surfactant (in the examples, other surfactants not having a polyoxyalkylene chain). The amount of residual surfactant in these polymer particles is 0.05 parts by mass or less (0.005 to 0.036 parts by mass in the examples) per 100 parts by mass of resin fine particles. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 051814 [Patent Document 2] JP 2006-233055 A Summary of the Invention [Problem to be solved by the invention]

[0007] 2. Description of the Related Art Known optical films, such as light diffusion films and antiglare films, are formed by coating a resin composition containing polymer particles, a binder and an organic solvent on a film substrate. When preparing an optical film in this manner, it is necessary that the polymer particles are uniformly and stably dispersed in the resin composition and in the dried coating film obtained therefrom so as to obtain stable optical properties. Furthermore, from the viewpoint of productivity, it is preferable that the time required for the polymer particles to be uniformly and stably dispersed in the resin composition is short.

[0008] The polymer particles disclosed in Patent Document 1 may require a long time for uniformly and stably dispersing in a resin composition depending on the type of other surfactant contained in the polymer particles, the amount of the surfactant remaining on the surface, and the amount of the non-volatile component remaining on the surface. When the polymer particles disclosed in Patent Document 2 are applied to a film substrate from a resin composition to form a coating film, the dispersion state of the polymer particles in the resin composition becomes unstable and non-uniform, and localized aggregation may occur. As a result, the polymer particles do not spread uniformly throughout the coating film formed on the film substrate, resulting in non-uniform optical properties of the optical film, and in some cases, the desired optical properties cannot be obtained throughout the entire optical film.

[0009] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide polymer particles which are uniformly and stably dispersed (excellent dispersibility and dispersion stability) in a resin composition and in a dried coating film obtained therefrom, and which require a short time for the polymer particles to be uniformly and stably dispersed in the resin composition. [Means for solving the problem]

[0010] Means for Solving the Problems The present inventors have conducted intensive research in view of the above problems and have found that in a resin composition containing polymer particles, the dispersion stability of the polymer particles correlates with the change in viscosity over time. The present inventors have discovered that in order to achieve high dispersion stability and to shorten the time until the dispersion becomes stable, it is important to optimize the type and solubility parameter (SP value) of the surfactant contained in the polymer particles, the amount of surface residue thereof, and the amount of surface residue of non-volatile components, and that this makes it possible to obtain polymer particles that are uniformly and stably dispersed (excellent dispersibility and dispersion stability) in a resin composition containing the polymer particles and in a dried coating film obtained therefrom, and have thus completed the present invention.

[0011] Specifically, the present invention is as follows. [1] (a) The content of a surfactant having a solubility parameter (SP value) of 9.0 to 12.0 and a polyoxyalkylene chain per unit surface area of ​​the polymer particle is 1.0 × 10 -3 ~6.0×10 -3 g / m 2 , (b) The content of a surfactant having a solubility parameter (SP value) of 9.0 to 12.0 and having no polyoxyalkylene chain is 5.0 × 10 per unit surface area of ​​the polymer particle. -5 ~13.0×10 -5 g / m 2 , (c) The amount of surface residue of non-volatile components is 2.0 × 10 per unit surface area of ​​polymer particles. -3 g / m 2 below, The polymer particles are [2] The polymer particles according to [1], having a volume average particle size of 1 to 20 μm, and a coefficient of variation (CV value) of the particle size of the polymer particles calculated by the following formula being 15% or less. Coefficient of variation of particle size of polymer particles (CV value) = (Standard deviation of volume-based particle size distribution of polymer particles ÷ Volume average particle size of polymer particles) × 100 [3] The polymer particles according to [1] or [2], wherein the surfactant having a polyoxyalkylene chain and an SP value of 9.0 to 12.0 is a phosphate-based anionic surfactant. [4] The polymer particles according to any one of [1] to [3] above, which are composed of one or more polymers selected from the group consisting of (meth)acrylic polymers, styrene polymers, and (meth)acrylic-styrene copolymers. [5] Polymer particles according to any one of [1] to [4], which are used for optical members. [6] Polymer particles of any one of [1] to [4] used as a paint additive. [7] Polymer particles of any one of [1] to [4] used as an antiblocking agent. [8] [1] to [4] A resin composition comprising polymer particles and a resin binder. [9] An optical member having a layer of the resin composition [8] on a substrate. Effect of the Invention

[0012] The polymer particles of the present invention have excellent dispersibility and dispersion stability in a resin composition containing the polymer particles, a binder, and an organic solvent, and also have excellent workability because the time required for the polymer particles to be uniformly and stably dispersed in the resin composition is shortened. In addition, even when the resin composition is applied to form a coating film, the dispersibility and dispersion stability of the polymer particles are maintained, so that excessive aggregation of the polymer particles during coating film formation can be suppressed. Therefore, the polymer particles are uniformly spread over the entire coating film formed on the film substrate, and the coating film can be imparted with optical properties such as stable light diffusibility and antiglare properties without unevenness. Furthermore, it is possible to adjust the dispersibility of the polymer particles in the resin composition by the type of surfactant contained in the polymer particles (for example, the presence or absence of a polyoxyalkylene chain, the solubility parameter (SP value) of the surfactant, etc.), the amount of the surfactant per unit surface area of ​​the polymer particles, and the amount of surface residue of non-volatile components per unit surface area of ​​the polymer particles. Therefore, it is no longer necessary to change the monomer composition of the polymer particles and adjust the refractive index accordingly, as has been conventionally done, in order to adjust the dispersibility of the polymer particles, and the workability can be further improved. Furthermore, since the polymer particles of the present invention have a small difference in the surface state between the polymer particles, when the polymer particles are mixed with a resin binder and an organic solvent to form a resin composition, the polymer particles have excellent dispersion uniformity in the resin composition. Also, since the change in the surface state of the polymer particles over time and the difference in the surface state between production lots of the polymer particles can be reduced, the quality stability is excellent, and the difference in the dispersion state between production lots of the resin composition is small, resulting in excellent dispersion stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Polymer particles] In the present invention, the solubility parameter (SP value) means a solubility parameter δ calculated by the following formula (1) using ΔF and Δv values ​​of various atomic groups by Okitsu Toshinao in Table 1 below, which is described in "Adhesion", Polymer Publishing Society, Vol. 40, No. 8 (1996), pp. 342-350. In the case of a mixed solvent or a copolymer, the solubility parameter δ means a solubility parameter δ calculated by the following formula (2). δ=ΣΔF / ΣΔv (1) δmix=φ1δ1+φ2δ2+···φnδn (2) In formula (1), ΔF represents ΔF in the following Table 1, and Δv represents the molar volume Δv in the following Table 1. In formula (2), φ represents a volume fraction or a molar fraction, and φ1+φ2+···φn=1.

[0014] [Table 1] In this specification, the solubility parameter calculated as above may be simply referred to as the SP value. The present invention will be described in detail below.

[0015] <Polymer> The polymer constituting the polymer particles of the present invention is not particularly limited, and examples thereof include one or more types selected from the group consisting of vinyl polymers (acrylic polymers, styrene polymers, acrylic-styrene polymers, olefin polymers, halogenated vinyl polymers, etc.), polyester polymers, polyamide polymers, polyurethane polymers, etc. Among these, vinyl polymers which are copolymers of a monofunctional vinyl monomer having one ethylenically unsaturated group and a polyfunctional vinyl monomer having two or more ethylenically unsaturated groups are preferred.

[0016] (Monofunctional vinyl monomer) As the monofunctional vinyl monomer, for example, one or more monomers selected from the group consisting of (meth)acrylic acid ester monomers, aromatic vinyl monomers, fatty acid vinyl ester monomers, halogenated olefin monomers, vinyl cyanide monomers, unsaturated carboxylic acid monomers, unsaturated polycarboxylic acid ester monomers, unsaturated carboxylic acid amide monomers, and methylolated unsaturated carboxylic acid amide monomers can be used. In this specification, the (meth)acrylic acid ester monomer means an acrylic acid ester monomer or a methacrylic acid ester monomer. Examples of the (meth)acrylic acid ester monomer include one or more selected from the group consisting of alkyl (meth)acrylate monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; (meth)acrylic acid esters having an epoxy group (glycidyl group) such as glycidyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; and (meth)acrylic acid esters having an amino group such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate.

[0017] The aromatic vinyl monomer may be, for example, one or more selected from the group consisting of styrene, α-methylstyrene, vinyltoluene, ethylvinylbenzene, and the like. As the fatty acid vinyl ester monomer, for example, one or more types selected from the group consisting of vinyl acetate, vinyl propionate, vinyl versatate, and the like can be used. As the halogenated olefin monomer, for example, one or more types selected from the group consisting of vinyl chloride, vinylidene chloride, tetrafluoroethylene, vinylidene fluoride, and the like can be used. As the vinyl cyanide monomer, for example, one or more types selected from the group consisting of (meth)acrylonitrile and the like can be used. The unsaturated carboxylic acid monomer includes an unsaturated carboxylic acid, a salt thereof, or an anhydride thereof, and for example, one or more types selected from the group consisting of (meth)acrylic acid, crotonic acid, citraconic acid, itaconic acid, maleic acid, fumaric acid, ammonium or metal salts thereof, maleic anhydride, etc. can be used.

[0018] The unsaturated polycarboxylate monomer includes unsaturated dicarboxylate monoesters, their salts, and unsaturated dicarboxylate diesters, and for example, one or more types selected from the group consisting of monobutyl maleate, ammonium or metal salts thereof, dimethyl maleate, and the like can be used. As the unsaturated carboxylic acid amide monomer, for example, one or more types selected from the group consisting of (meth)acrylamide, diacetone (meth)acrylamide, and the like can be used. As the methylolated unsaturated carboxylic acid amide monomer, for example, one or more selected from the group consisting of N-methylol acrylamide, N-methylol methacrylamide, methylolated diacetone acrylamide, and ethers of these monomers with alcohols having 1 to 8 carbon atoms (for example, N-isobutoxymethyl acrylamide), etc. can be used.

[0019] (Multifunctional vinyl monomer) The polyfunctional vinyl monomer is not particularly limited as long as it is a monomer having two or more ethylenically unsaturated groups. For example, one or more selected from the group consisting of allyl (meth)acrylate, divinylbenzene, diallyl phthalate, triallyl cyanurate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, etc. can be used.

[0020] The polymer particles of the present invention are preferably composed of at least one polymer selected from the group consisting of a (meth)acrylic polymer, a styrene polymer, and a (meth)acrylic-styrene copolymer, which allows the realization of polymer particles with high light transmittance. The (meth)acrylic polymer is a polymer of a (meth)acrylic acid ester monomer, or a copolymer of a (meth)acrylic acid ester monomer and a vinyl monomer other than a (meth)acrylic acid ester monomer and a styrene monomer. The styrene polymer is a polymer of a styrene monomer, or a copolymer of a styrene monomer and a vinyl monomer other than a (meth)acrylic acid ester monomer and a styrene monomer. The (meth)acrylic-styrene copolymer is a copolymer of a (meth)acrylic acid ester monomer and a styrene monomer, or a copolymer of a (meth)acrylic acid ester monomer, a styrene monomer, and a vinyl monomer other than these.

[0021] Among these, polymer particles composed of a (meth)acrylic-styrene copolymer are preferred in terms of light diffusibility and antiglare properties, and polymer particles having a specific gravity of more than 1.0 are more preferred. The specific gravity of the polymer particles is a measured value obtained by measuring according to Method A of JIS K5101-11-1. Specifically, the specific gravity was measured in a thermostatic room at 20° C. as follows. A Wardon-type pycnometer with a capacity of 50 ml was completely filled with ethanol, and the mass of the pycnometer including the contents at this time was weighed and defined as A (g). Next, the ethanol in the pycnometer was discarded and the pycnometer was emptied, and then about 3 g of polymer particles as a sample was transferred into the pycnometer, and the mass of the transferred polymer particles was weighed and defined as B (g). Ethanol was further added to the pycnometer to completely fill it with polymer particles and ethanol. The mass of the pycnometer including the contents at this time was designated as Cg. The specific gravity of the polymer particles was calculated according to the following formula. Specific gravity (g / ml) = B × 0.7950 / (A - C + B)

[0022] In addition, the polymer constituting the polymer particles is preferably a copolymer (crosslinked polymer) of a monofunctional vinyl monomer and a polyfunctional vinyl monomer. In the present invention, it is particularly preferable that the polymer constituting the polymer particles is a (meth)acrylic-styrene-based crosslinked polymer from the viewpoints of light diffusibility and antiglare property. The amount of the structural unit derived from the polyfunctional vinyl monomer in the crosslinked polymer is in the range of 1 to 70% by mass, preferably 3 to 60% by mass, more preferably 5 to 50% by mass based on 100% by mass of the crosslinked polymer. When the amount of the structural unit derived from the polyfunctional vinyl monomer is less than 1% by mass, the crosslinking degree of the polymer decreases. Therefore, when the polymer particles are mixed with a binder and a solvent to form a resin composition, the polymer particles may swell, the viscosity of the resin composition may increase, and there is a risk of deterioration in coating workability. Furthermore, as a result of the decrease in the crosslinking degree of the polymer, in applications where the polymer particles are mixed with a binder and molded (so-called kneading applications), when heat is applied to the polymer particles during mixing or molding, the polymer particles are likely to dissolve or deform. When the amount of the structural unit derived from the polyfunctional vinyl monomer is more than 70% by mass, an improvement in the effect commensurate with the amount of the polyfunctional vinyl monomer used is not recognized, and the production cost may increase.

[0023] <Surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0> In the surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0, the more preferable range of the SP value is 9.1 to 11.9, more preferably 9.3 to 11.7, and most preferably 9.6 to 11.2. In addition, examples of the alkylene group in the polyoxyalkylene chain include alkylene groups having 2 to 6 carbon atoms, preferably an ethylene group, a propylene group, a trimethylene group, and a butylene group, and particularly preferably an ethylene group. The surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0 may be any of anionic, cationic, nonionic and amphoteric surfactants, so long as the SP value is within the range of 9.0 to 12.0. In the present invention, since the dispersion of the vinyl monomer in the liquid medium can be more stably ensured during the polymerization of the vinyl monomer, and polymer particles having a uniform particle size can be obtained, it is preferable to use at least one of an anionic surfactant and a nonionic surfactant, and more preferable to use at least an anionic surfactant having a polyoxyalkylene chain. This can prevent the occurrence of aggregation during the polymerization reaction, and ensure the dispersion stability.

[0024] As the anionic surfactant having a polyoxyalkylene chain, any of the known anionic surfactants such as fatty acid salt type, sulfate salt type, sulfonate salt type, phosphate salt type, and phosphate type can be used. For example, one or more selected from the group consisting of polyoxyethylene alkyl phenyl ether sulfates, polyoxyethylene alkyl ether sulfates such as polyoxyethylene lauryl ether sodium sulfate, polyoxyethylene alkyl sulfates, polyoxyethylene styrenated phenyl ether sulfates such as ammonium polyoxyethylene styrenated phenyl ether sulfate, polyoxyethylene alkyl phenyl ether phosphates such as polyoxyethylene nonyl phenyl ether phosphate (e.g. sodium polyoxyethylene nonyl phenyl ether phosphate), polyoxyethylene styrenated phenyl ether phosphate, polyoxyethylene alkyl ether phosphate, and the like can be used.

[0025] As the nonionic surfactant having a polyoxyalkylene chain, any of the known nonionic surfactants such as ester type, ether type, and ester-ether type can be used. For example, one or more selected from the group consisting of polyoxyethylene alkyl ethers such as polyoxyethylene tridecyl ether, polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octyl phenyl ether, polyoxyethylene styrenated phenyl ether, polyoxyethylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene alkylamines, oxyethylene-oxypropylene block polymers, and the like can be used.

[0026] Among these, it is preferable to use one or more of phosphate-based anionic surfactants such as polyoxyethylene alkylphenyl ether phosphates such as polyoxyethylene nonylphenyl ether phosphates (e.g., sodium polyoxyethylene nonylphenyl ether phosphate), polyoxyethylene styrenated phenyl ether phosphates, and polyoxyethylene alkyl ether phosphates. As such phosphate-based anionic surfactants, for example, one or more selected from commercially available products such as Plysurf (AL, A210G, A208F, etc.) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. and Phosphanol (LO-529, etc.) manufactured by Toho Chemical Industry Co., Ltd., and salts thereof can be used.

[0027] The content of the surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0 is 1.0 × 10 per unit surface area of ​​the polymer particle. -3 ~6.0×10 -3 g / m 2 and preferably 1.1×10 -3 ~4.25×10 -3 g / m 2 , more preferably 1.4×10 -3 ~2.8×10 -3 g / m 2 This makes it possible to improve the dispersibility and dispersion stability of the polymer particles when a resin composition containing the polymer particles is formed. In addition, it becomes possible to adjust the dispersibility and dispersion stability of the polymer particles without changing the monomer composition of the polymer particles. Incidentally, the inventors have found that when the content of the surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0 is 4.4×10 -3 ~6.0×10 -3 g / m 2 even per unit surface area of the polymer particles, the dispersibility and dispersion stability of the polymer particles can be enhanced when forming a resin composition containing the polymer particles, and it is possible to adjust the dispersibility and dispersion stability without changing the monomer composition of the polymer particles.

[0028] The means for incorporating a surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0 into the polymer particles is not particularly limited. For example, there are a method of mixing the polymer particles and the surfactant, a method of coexisting the surfactant during the formation of the polymer particles, and the like. In the present invention, in particular, in the presence of a surfactant having a polyoxyalkylene chain, a vinyl-based polymer is polymerized, and if necessary, the content is adjusted to thereby incorporate (retain) a surfactant having a polyoxyalkylene chain into the polymer particles. It is preferable to use the method.

[0029] In particular, it is preferable to perform seed polymerization in the presence of seed particles, a vinyl-based monomer, and a surfactant having a polyoxyalkylene chain, and adjust the content in a washing step or the like. The polymer particles obtained by seed polymerization have little variation in particle diameter, and when used for optical members such as an antiglare film and a light diffusion film, optical properties such as the antiglare property and light diffusion property of the optical member can be improved.

[0030] <Surfactant having no polyoxyalkylene chain with an SP value of 9.0 to 12.0> In the surfactant having no polyoxyalkylene chain with an SP value of 9.0 to 12.0, a more preferable range of the SP value is 9.0 to 11.8, still more preferably 9.1 to 11.5, and most preferably 9.2 to 11.4. The surfactant having an SP value of 9.0 to 12.0 and no polyoxyalkylene chain may be any of anionic, cationic, nonionic and amphoteric surfactants, so long as the SP value is within the range of 9.0 to 12.0. In the present invention, when a vinyl monomer is polymerized in the presence of a surfactant, it is more preferable to use at least one of an anionic surfactant and a nonionic surfactant, since the dispersion of the vinyl monomer in a liquid medium can be more stably ensured and polymer particles having a uniform particle size can be obtained. This makes it possible to prevent the occurrence of aggregation during the polymerization reaction and ensure dispersion stability.

[0031] As the anionic surfactant having no polyoxyalkylene chain, any of the known anionic surfactants such as fatty acid salt type, sulfate ester salt type, sulfonate salt type, and phosphate ester salt type can be used. For example, one or more selected from the group consisting of fatty acid soaps such as sodium oleate and castor oil potassium soap, alkyl sulfate ester salts such as sodium lauryl sulfate and ammonium lauryl sulfate, alkyl benzene sulfonates such as sodium dodecylbenzene sulfonate, alkyl naphthalene sulfonates, alkanesulfonates, dialkyl sulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate and sodium dioctyl sulfosuccinate, alkenyl succinates such as sodium alkenyl succinate (mono- or di-), alkyl phosphate ester salts, and naphthalene sulfonate-formaldehyde condensates can be used.

[0032] As the nonionic surfactant having no polyoxyalkylene chain, any of the known nonionic surfactants such as ester type, ether type, and ester-ether type can be used. For example, one or more selected from the group consisting of polyoxyalkylene alkyl ethers such as polyoxyalkylene tridecyl ethers in which the alkylene group has 3 or more carbon atoms, sorbitan fatty acid esters, glycerin fatty acid esters, isopropyl palmitate, sorbitan trioleate, and other fatty acid esters can be used.

[0033] As the cationic surfactant having no polyoxyalkylene chain, any of the known cationic surfactants such as amine salt type and quaternary ammonium salt type can be used, and water-soluble cationic surfactants are particularly advantageous in terms of handling. For example, one or more compounds selected from the group consisting of alkylamine salts such as laurylamine acetate and stearylamine acetate, alkyltrimethylammonium chlorides such as lauryltrimethylammonium chloride, hexadecyltrimethylammonium chloride, cocoyltrimethylammonium chloride and dodecyltrimethylammonium chloride, and alkyldimethylbenzylammonium chlorides such as hexadecyldimethylbenzylammonium chloride and lauryldimethylbenzylammonium chloride can be used.

[0034] As the amphoteric surfactant having no polyoxyalkylene chain, for example, one or more types selected from the group consisting of lauryl dimethylamine oxide, phosphate surfactants, phosphite surfactants, and the like can be used.

[0035] Among these, it is preferable to use one or more anionic surfactants having no polyoxyalkylene chain selected from the group consisting of dialkyl sulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, alkenyl succinates such as sodium (mono- or di-)alkenyl succinate, alkyl phosphates, and alkyl sulfates such as sodium lauryl sulfate, and one or more nonionic surfactants having no polyoxyalkylene chain selected from the group consisting of fatty acid esters such as isopropyl palmitate and sorbitan trioleate.

[0036] The content of the surfactant having no polyoxyalkylene chain and an SP value of 9.0 to 12.0 is 5.0 × 10 per unit surface area of ​​the polymer particle. -5 ~13.0×10 -5 g / m 2 and preferably 5.2×10 -5 ~12.7×10 -5 g / m 2 and particularly preferably 7.3×10 -5 ~10.4×10 -5 g / m 2 This makes it possible to improve the dispersibility and dispersion stability of the polymer particles when a resin composition containing the polymer particles is formed. In addition, it becomes possible to adjust the dispersibility and dispersion stability of the polymer particles without changing the monomer composition of the polymer particles.

[0037] The method of incorporating the surfactant having a SP value of 9.0 to 12.0 and no polyoxyalkylene chain into the polymer particles is not particularly limited. For example, the method of mixing the polymer particles with the surfactant, the method of allowing the surfactant to coexist during the formation of the polymer particles, etc. can be mentioned. In the present invention, it is particularly preferable to use a method in which a vinyl polymer is polymerized in the presence of a surfactant and the content is adjusted as necessary to contain (remain) the surfactant in the polymer particles. In particular, it is preferable to carry out seed polymerization in the presence of seed particles, a vinyl monomer, and a surfactant, and adjust the content by a washing step, etc. The polymer particles obtained by seed polymerization have little variation in particle size, and when used for optical components such as antiglare films and light diffusion films, the optical properties such as antiglare properties and light diffusion properties of the optical components can be improved.

[0038] <Non-volatile components> The non-volatile components in the polymer particles of the present invention refer to the non-volatile components contained in the supernatant liquid after the polymer particles are dispersed in water, centrifuged, and separated into the polymer particles and the supernatant liquid. Specifically, 15.0 g of water is added to 5.0 g of polymer particles, and the polymer particles are dispersed in water by dispersing the particles using an ultrasonic cleaner for 60 minutes. The particles are then placed in a centrifuge tube having an inner diameter of 24 mm and centrifuged using a centrifuge under conditions of a K factor of 6943 and a rotation time of 30 minutes. The non-volatile components are contained in the supernatant recovered.

[0039] Such non-volatile components are components that remain without dissipation even after heating at 110°C and 1 atmosphere for 10 hours. For example, when the polymer particles are obtained by seed polymerization, they are by-products such as polymerization products in which monomers that were not absorbed by the seed particles are polymerized. For example, they include minute components with a diameter of 1 μm or less contained in the polymer particles.

[0040] The amount of surface residue of non-volatile components per unit surface area of ​​a polymer particle is calculated using the content of non-volatile components in the polymer particle and the specific surface area of ​​the polymer particle according to the following formula. The amount of non-volatile residue on the surface of polymer particles per unit surface area (g / m 2 ) = (content of non-volatile components in polymer particles (g / 1g of polymer particles) ÷ specific surface area of ​​polymer particles (m 2 / g) The amount of non-volatile components remaining on the surface of the polymer particles of the present invention is 2.0×10 -3 g / m 2 Less than or equal to 0.01 x 10 -3 ~2.0×10 -3g / m 2 , more preferably 0.04×10 -3 ~1.95×10 -3 g / m 2 , and more preferably 0.7×10 -3 ~1.3×10 -3 g / m 2 It is. This makes it possible to reduce the variation in the amount of non-volatile components present on the surface of each polymer particle, and improve the dispersion uniformity when the polymer particles are dispersed in a medium, particularly in a mixture of an organic solvent and a binder.

[0041] <Volume average particle size> The volume average particle diameter of the polymer particles of the present invention is, for example, 1 to 20 μm, preferably 1.5 to 15 μm, and more preferably 1.5 to 10 μm, whereby, when the polymer particles are used for optical members such as antiglare films and light diffusion films, the optical properties such as antiglare properties and light diffusion properties of the optical members can be improved. In the present invention, the volume average particle size of the polymer particles refers to the arithmetic average of the volume-based particle size distribution measured by the Coulter method, for example, the method described in the Examples.

[0042] <Coefficient of variation of particle size (CV value)> The coefficient of variation (CV value) of the particle size of the polymer particles of the present invention is calculated by the following formula. Coefficient of variation of particle size of polymer particles (CV value) = (Standard deviation of volume-based particle size distribution of polymer particles ÷ Volume average particle size of polymer particles) × 100 In the present invention, the coefficient of variation (CV value) of particle size is preferably 15% or less, more preferably 12% or less, and further preferably 11% or less, which can further improve the dispersion uniformity of the polymer particles.

[0043] <Gel fraction> The gel fraction of the polymer particles of the present invention is 90% or more, preferably 94% or more, more preferably 96% or more, and further preferably 97% or more. If the gel fraction is less than 90%, sufficient solvent resistance cannot be ensured, and for example, when the polymer particles are mixed with an organic solvent together with a binder and coated on a film substrate to form an optical film such as an antiglare film or a light diffusion film, the polymer particles may dissolve in the organic solvent, and optical properties such as light diffusion and antiglare properties may not be sufficiently obtained. Note that the gel fraction in this specification refers to the gel fraction measured by the method described in the Examples, for example.

[0044] <Refractive index> The refractive index of the polymer particles of the present invention is preferably 1.490 to 1.600. As a result, when the polymer particles having the above configuration are used in optical components such as antiglare films and light diffusion films, the optical components can have good optical properties (for example, light transmittance, antiglare properties, light diffusion properties, etc.). Up until now, polymer particles produced from a monomer having a high refractive index of a homopolymer (e.g., a styrene-based monomer) and a highly hydrophilic monomer have been difficult to realize polymer particles having a refractive index of 1.570 to 1.600, because the highly hydrophilic monomer generally has a low refractive index of the homopolymer (e.g., 1.488 or less). In contrast, the polymer particles of the present invention can be imparted with hydrophilicity without the need for the addition of a highly hydrophilic monomer, so that polymer particles having a refractive index of 1.570 to 1.600 and hydrophilicity can be easily obtained.

[0045] [Method of producing polymer particles] Examples of the method for producing the polymer particles of the present invention include a method in which the polymer particles are mixed with a surfactant, and a method in which a surfactant is made to coexist during the formation of the polymer particles. In the present invention, it is particularly preferable to use a method in which a vinyl polymer is polymerized in the presence of a surfactant and the content is adjusted as necessary to contain (remain) the surfactant in the polymer particles. In particular, (i) in the presence of a surfactant containing a surfactant having a polyoxyalkylene chain and an SP value of 9.0 to 12.0 in a liquid medium, and a surfactant having no polyoxyalkylene chain, a vinyl monomer is polymerized to obtain a crude product containing polymer particles containing the surfactant and the medium; (ii) the crude product is put into a filter, the medium contained in the crude product is removed by passing it through the filter medium of the filter medium, and the polymer particles contained in the crude product are held on the filter medium in a solid-liquid separation step; (iii) a washing liquid is put into the filter medium holding the polymer particles on the filter medium, the polymer particles on the filter medium are contacted with the washing liquid, and the washing liquid is passed through the filter medium to remove the washed polymer particles on the filter medium; (iv) if necessary, a drying step and / or a classification step, and a method including the steps are preferred.

[0046] As the polymerization step (i) above, it is particularly preferred to carry out seed polymerization in the presence of seed particles, a vinyl monomer and a surfactant, and adjust the content by a washing step, etc. The polymer particles obtained by seed polymerization have little variation in particle size, and when used for optical components such as antiglare films and light diffusion films, the optical properties such as antiglare properties and light diffusion properties of the optical components can be improved.

[0047] In addition, in the production of the polymer particles of the present invention, the above-mentioned solid-liquid separation process and washing process may affect the uniformity of the amount of residual components on the polymer particle surface and the resulting uniformity of the surface state. If these processes become unstable, they will have a negative effect on the removal of unnecessary surfactants (surface surfactants having excess polyoxyalkylene chains that do not contribute to the modification of the polymer particle surface and other surfactants used as needed) used in the production of the polymer particles and polymer dispersion stabilizers used as needed, causing variations in the amount of residual components on the polymer particle surface. Each step of the method for producing polymer particles of the present invention will be described in detail below.

[0048] <Polymerization process> The polymerization process is a process of polymerizing a vinyl monomer in the presence of a surfactant containing a surfactant having an SP value of 9.0 to 12.0 and having a polyoxyalkylene chain and a surfactant having an SP value of 9.0 to 12.0 and not having a polyoxyalkylene chain in a liquid medium to obtain a crude product containing polymer particles containing the surfactant and the medium.

[0049] As the liquid medium, any of water, an organic solvent, and a mixture thereof can be used. In the present invention, an aqueous medium is preferable, and for example, water, a lower alcohol having 5 or less carbon atoms such as methyl alcohol and ethyl alcohol, a mixture of water and a lower alcohol, etc. can be used. As the surfactant having an SP value of 9.0 to 12.0 and having a polyoxyalkylene chain, the surfactant described in <Surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0> in the above [Polymer Particles] is used. As the surfactant having an SP value of 9.0 to 12.0 and not having a polyoxyalkylene chain, the surfactant described in <Surfactant not having a polyoxyalkylene chain with an SP value of 9.0 to 12.0> in the above [Polymer Particles] is used. As the vinyl monomer and its composition, the vinyl monomer and its composition described in <Polymer> in the above [Polymer Particles] are used.

[0050] The usage amounts of the surfactant having an SP value of 9.0 to 12.0 and having a polyoxyalkylene chain and the surfactant having an SP value of 9.0 to 12.0 and not having a polyoxyalkylene chain in the polymerization of the vinyl monomer are not particularly limited, but as the total amount of the surfactant, it is 0.01 to 10 parts by mass, preferably 0.01 to 5 parts by mass with respect to 100 parts by mass of the vinyl monomer. Further, it is preferable to contain 50 to 99% by mass, preferably 70 to 99% by mass of the surfactant having an SP value of 9.0 to 12.0 and having a polyoxyalkylene chain with respect to the whole surfactant. If the total amount of the surfactant is less than the above range, the polymerization stability may be decreased, and it may be difficult to adjust the amount of the surfactant contained in the polymer particles. If the amount of the surfactant used is more than the above range, it is uneconomical in terms of cost, and it may be difficult to adjust the amount of each surfactant contained in the polymer particles to the specified range.

[0051] In the present invention, at least an anionic surfactant having a polyoxyalkylene chain and an SP value of 9.0 to 12.0, and a nonionic surfactant having a polyoxyalkylene chain and an SP value of 9.0 to 12.0 are used, since dispersion stability can be ensured during polymerization of a vinyl monomer in a liquid medium and polymer particles having a uniform particle size can be obtained.

[0052] The method for polymerizing the vinyl monomer is not particularly limited as long as it is a known polymerization method using a liquid medium and a surfactant, such as emulsion polymerization, suspension polymerization, seed polymerization, etc. Emulsion polymerization is a polymerization method in which a liquid medium, a vinyl monomer that is difficult to dissolve in the medium, and a surfactant (emulsifier) ​​are mixed, and a polymerization initiator that is soluble in the medium is added to the mixture to carry out polymerization. Emulsion polymerization can reduce the variation in particle size of the resulting polymer particles. Suspension polymerization is a polymerization method in which a vinyl monomer and an aqueous medium such as water are mechanically stirred to suspend the vinyl monomer in the aqueous medium and polymerize it. By suspension polymerization, polymer particles having a small particle size and a relatively uniform particle size can be obtained.

[0053] Seed polymerization is a method in which, when starting polymerization of a vinyl monomer, seed particles made of a polymer of a vinyl monomer that has been separately prepared are introduced to carry out polymerization. For example, polymer particles made of a polymer of a vinyl monomer are used as seed particles, the seed particles are made to absorb the vinyl monomer in an aqueous medium, and the vinyl monomer is polymerized within the seed particles. This allows the seed particles to grow, and polymer particles having a particle size larger than that of the original seed particles can be obtained. In particular, it is preferable to perform seed polymerization of the vinyl monomer in the presence of the seed particles and a surfactant in a liquid medium to obtain a crude product containing the surfactant-containing polymer particles and the medium. Among these polymerization methods, emulsion polymerization or seed polymerization is preferred, and seed polymerization is most preferred, since it results in the least variation in particle size of the resulting polymer particles. A general method for seed polymerization will be described below, but the polymerization method in the production method of the present invention is not limited to this method.

[0054] First, an emulsion (suspension) containing an aqueous medium, a vinyl monomer, and a surfactant is prepared. Here, the aqueous medium is water or a mixture of water and an organic solvent (for example, a lower alcohol having 5 or less carbon atoms). The surfactant includes a surfactant having a SP value of 9.0 to 12.0 and a polyoxyalkylene chain, and a surfactant having a SP value of 9.0 to 12.0 and no polyoxyalkylene chain. The amount of the surfactant used is preferably within a range of 0.01 to 5 parts by mass based on 100 parts by mass of the vinyl monomer. The emulsion (suspension) can be prepared by a known method. For example, the emulsion can be obtained by adding a vinyl monomer and a surfactant to an aqueous medium and dispersing the mixture with a microemulsifier such as a homogenizer, an ultrasonic processor, or a Nanomizer (registered trademark). Incidentally, it is preferable that the particle size of the droplets of the vinyl monomer present in the obtained emulsion is smaller than the particle size of the seed particles to be added subsequently, since the droplets are efficiently absorbed by the seed particles.

[0055] Next, seed particles are added to the resulting emulsion (suspension). The seed particles may be added to the emulsion as they are, or may be added to the emulsion in a form dispersed in an aqueous medium. When the seed particles are added to the emulsion, the vinyl monomer is absorbed into the seed particles. A typical method for causing the seed particles to absorb the vinyl monomer is to stir the emulsion at room temperature (about 20°C) for 1 to 12 hours. In addition, in order to promote the absorption of the vinyl monomer into the seed particles, the emulsion may be heated to about 30 to 50°C.

[0056] When the seed particles absorb the vinyl monomer, the seed particles swell. The mixing ratio of the vinyl monomer to the seed particles is preferably within a range of 5 to 300 parts by mass, more preferably 50 to 250 parts by mass, of the vinyl monomer per 1 part by mass of the seed particles. If the mixing ratio of the vinyl monomer is smaller than the above range, the increase in particle size due to polymerization is small, and the production efficiency is reduced. If the mixing ratio of the vinyl monomer is larger than the above range, the vinyl monomer is not completely absorbed into the seed particles, and suspension polymerization occurs independently in the aqueous medium, which may result in the production of polymer particles with abnormal particle sizes that are not intended. The completion of absorption of the vinyl monomer into the seed particles can be determined by observing the increase in particle size under an optical microscope. Next, the vinyl monomer absorbed in the seed particles is polymerized to obtain polymer particles. The step of absorbing the vinyl monomer into the seed particles and polymerizing the same may be repeated several times to obtain polymer particles.

[0057] In the polymerization of the vinyl monomer, a polymerization initiator may be used as necessary. The polymerization initiator may be mixed with the vinyl monomer in advance and then dispersed in the aqueous medium, or both the polymerization initiator and the vinyl monomer may be dispersed separately in the aqueous medium. The polymerization initiator used is not particularly limited. For example, organic peroxides such as benzoyl peroxide, lauroyl peroxide, o-chlorobenzoyl peroxide, o-methoxybenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-ethylhexanoate, and di-tert-butyl peroxide, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,3-dimethylbutyronitrile), and 2,2'-azobis(2-methylbutyronitride) can be used. Examples of the polymerization initiator include at least one selected from the group consisting of azo compounds such as 2,2'-azobis(2,3,3-trimethylbutyronitrile), 2,2'-azobis(2-isopropylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), (2-carbamoylazo)isobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and dimethyl-2,2'-azobisisobutyrate. The polymerization initiator is preferably used in an amount of 0.1 to 1.0 part by mass relative to 100 parts by mass of the vinyl monomer.

[0058] The polymerization temperature and polymerization time of the seed polymerization can be appropriately selected depending on the type of vinyl monomer and the type of polymerization initiator used as necessary. The polymerization temperature can be, for example, 25 to 110° C., preferably 50 to 100° C. The polymerization time can be, for example, 1 to 12 hours. The polymerization reaction of the seed polymerization may be carried out under an atmosphere of an inert gas (eg, nitrogen) that is inert to the polymerization. In the production of the polymer particles of the present invention, the polymerization reaction of the seed polymerization is preferably carried out at elevated temperature after the vinyl monomer and the polymerization initiator used if necessary are completely absorbed into the seed particles.

[0059] In the seed polymerization, a polymer dispersion stabilizer may be added to the polymerization reaction system in order to improve the dispersion stability of the polymer particles. Examples of the polymer dispersion stabilizer include polyvinyl alcohol, polycarboxylic acid, celluloses (hydroxyethyl cellulose, carboxymethyl cellulose, etc.), polyvinylpyrrolidone, etc. In addition, the above polymer dispersion stabilizer may be used in combination with an inorganic water-soluble polymer compound such as sodium tripolyphosphate. Of these polymer dispersion stabilizers, it is preferable to use polyvinyl alcohol and polyvinylpyrrolidone. The amount of the polymer dispersion stabilizer added is preferably within the range of 1 to 10 parts by mass per 100 parts by mass of the vinyl monomer.

[0060] In order to suppress the generation of emulsion polymerization products (polymer particles with too small a particle size) in the aqueous medium during the polymerization reaction, a water-soluble polymerization inhibitor such as nitrites such as sodium nitrite, sulfites, hydroquinones, ascorbic acids, water-soluble vitamin B, citric acid, polyphenols, etc. may be added to the aqueous medium. When a polymerization inhibitor is used, the amount added is preferably within a range of 0.02 to 0.2 parts by mass relative to 100 parts by mass of the vinyl monomer.

[0061] The method for producing seed particles used in seed polymerization is not particularly limited, and dispersion polymerization, emulsion polymerization, soap-free emulsion polymerization (emulsion polymerization without using a surfactant as an emulsifier), seed polymerization, suspension polymerization, etc. can be used. In order to obtain polymer particles having a substantially uniform particle size by seed polymerization, it is necessary to first use seed particles having a substantially uniform particle size and to grow these seed particles substantially uniformly. The seed particles having a substantially uniform particle size as the raw material can be obtained by subjecting a vinyl monomer to emulsion polymerization, dispersion polymerization, etc. Preferably, emulsion polymerization, soap-free emulsion polymerization, seed polymerization, and dispersion polymerization are used.

[0062] In the polymerization for obtaining the seed particles, a polymerization initiator is used as necessary. Examples of the polymerization initiator include the polymerization initiators that can be used in the seed polymerization. The amount of the polymerization initiator used is preferably within a range of 0.1 to 3 parts by mass relative to 100 parts by mass of the vinyl monomer used for obtaining the seed particles. The weight average molecular weight of the obtained seed particles can be adjusted by adjusting the amount of the polymerization initiator used.

[0063] In the polymerization of the seed particles, a molecular weight regulator may be used to adjust the weight average molecular weight of the seed particles. As the molecular weight regulator, one or more selected from the group consisting of mercaptans such as n-octyl mercaptan and tert-dodecyl mercaptan, α-methylstyrene dimer, terpenes such as γ-terpinene and dipentene, halogenated hydrocarbons such as chloroform and carbon tetrachloride, etc. can be used. The weight average molecular weight of the obtained seed particles can be adjusted by adjusting the amount of the molecular weight regulator used.

[0064] <Solid-liquid separation process> The solid-liquid separation process in producing the polymer particles of the present invention is a process in which a crude product containing the surfactant-containing polymer particles obtained in the polymerization process and a medium is introduced into a filter, the medium contained in the crude product is removed by passing it through the filter material of the filter, and the polymer particles contained in the crude product are retained on the filter material, thereby performing solid-liquid separation.

[0065] In the solid-liquid separation process, the amount of medium passing through the filter medium per unit time is expressed by the following formula (3); X≦5.50×A (3) (In formula (3), X is the amount of media passing through the filter per unit time (kg / min), and A is the area of ​​the interface between the filter and the object to be filtered (m 2 ) It is preferable that the following is satisfied. In the solid-liquid separation process, the amount of medium passing through the filter medium per unit time is controlled to satisfy the above formula (3), so that unnecessary components such as by-products (emulsion polymerization products) generated during polymerization reaction, excess surfactant, polymer dispersion stabilizer used as needed, and additives such as polymerization inhibitor used as needed can be removed together with the medium.Therefore, the amount of surfactant and non-volatile components contained in the polymer particles remaining on the filter medium can be easily adjusted (reduced).

[0066] The filter used in the solid-liquid separation process is not particularly limited.For example, a pressure filter can be used that includes a pressure vessel having a cylindrical internal space, a filter medium arranged on the inner bottom of the pressure vessel, and a compressed gas supplying device that supplies compressed gas into the pressure vessel.In the pressure filter, the area (filtering area) of the bottom surface of the cylindrical internal space of the pressure vessel can be approximately the same as the area of ​​the interface between the filter medium and the filtered material (crude product).

[0067] The solid-liquid separation step using such a pressure filter can be, for example, the following method. (a) The crude product is charged in the form of a slurry solution into a pressure vessel of a pressure filter. (b) The crude product is loaded onto a filter medium in a pressure vessel. (c) Compressed gas is supplied to the space above the filter medium in the pressure vessel by a compressed gas supply device, thereby pressurizing the space above the filter medium inside the pressure vessel. (d) By pressurizing the upper space, the crude product is pressed against the filter medium, and the liquid medium contained in the crude product passes through the filter medium and is discharged outside the pressure vessel as filtrate, and a cake of polymer particles can be obtained on the filter medium.

[0068] The pressure vessel is preferably made of, for example, stainless steel and has a pressure resistance of 0.50 MPa or more. The filter material is not particularly limited as long as it can reliably collect polymer particles. For example, one or more types selected from the group consisting of filter cloth such as woven fabric and nonwoven fabric made of natural fiber, synthetic fiber, etc., wire mesh made of sintered metal, nonwoven fabric made of sintered metal, filter plate (porous plate) made of natural fiber, glass fiber, etc., mesh made of synthetic resin, filter paper, glass fiber filter, etc. are listed, and filter cloth is particularly preferred.

[0069] In the solid-liquid separation process, the pressurizing conditions when pressurizing the space above the filter medium in the pressure vessel using a pressure filter are not particularly limited as long as they satisfy the above formula (3). For example, it is preferable to pressurize so that the internal pressure of the pressure vessel is within the range of 0.01 MPa to 0.50 MPa. In the solid-liquid separation process, it is preferable that the internal pressure of the pressure vessel is kept almost constant from the start of pressurization to the end of the solid-liquid separation process so as to satisfy the above formula (3). In addition, the internal pressure of the pressure vessel gradually decreases after pressurization as the medium contained in the crude product passes through the filter medium. Specifically, when the medium passing through the filter medium becomes less or almost disappears, the compressed air pressure in the pressure vessel escapes from the bottom, making it difficult to maintain the internal pressure of the pressure vessel at the pressure when pressurized.

[0070] In the solid-liquid separation step, it is preferable to carry out the solid-liquid separation step until 70% by mass or more, preferably 75 to 85% by mass of the medium passes through the filter material, based on 100% by mass of the medium contained in the crude product put into the filter (pressure filter) (when all the crude product obtained in the polymerization step is put into the filter material, the amount of the medium used in the polymerization step). This makes it possible to remove unnecessary components such as by-products (emulsion polymerization products) generated during the polymerization reaction, excess surfactants, polymer dispersion stabilizers used as needed, and additives such as polymerization inhibitors used as needed. This makes it possible to easily adjust (reduce) the amounts of surfactants, non-volatile components, and unnecessary components contained in the polymer particles remaining on the filter material. In the solid-liquid separation process, if the amount of medium passing through the filter medium (discharge amount) is less than 70 mass% relative to 100 mass% of the amount of medium contained in the crude product, it may not be possible to sufficiently remove unnecessary components, and it may be difficult to adjust (reduce) the amount of surfactant and non-volatile components contained in the polymer particles remaining on the filter medium.

[0071] In the solid-liquid separation step, when a pressure filter is used as a filter, it is preferable that the amount of the medium contained in the crude product that is put into the pressure filter is 100% by mass, and when 70% by mass or more of the medium passes through the filter medium, and the internal pressure of the pressure-resistant container becomes 2 / 3 or less of the pressure when pressurized, the amount of unnecessary components remaining in the polymer particles that remain on the filter medium is reliably reduced.

[0072] In the solid-liquid separation step, the deliquation speed when removing the medium from the slurry consisting of the crude product containing the polymer particles and the medium is not particularly limited. For example, it is 0.025 to 0.095 kg / min m 2 , preferably 0.025 to 0.08 kg / min m 2 , more preferably 0.028 to 0.075 kg / min m 2 The range may be: If the drainage rate is too fast, it may not be possible to sufficiently remove unnecessary components contained in the polymer particles, and it may become difficult to adjust (reduce) the amount of surfactant and non-volatile components contained in the polymer particles. If the drainage rate is too slow, the solid-liquid separation step will take a long time, resulting in poor workability and the surfactant contained in the polymer particles may be lost more than necessary.

[0073] <Cleaning process> The washing step in producing the polymer particles of the present invention is a step in which a washing liquid is poured into the filter holding the polymer particles on the filter medium after the solid-liquid separation step, the polymer particles on the filter medium are brought into contact with the washing liquid, and the washing liquid is passed through the filter medium and removed, thereby obtaining washed polymer particles on the filter medium. The present inventors have found a method in which, in the washing step, the polymer particles on the filter medium (polymer particle cake) obtained in the solid-liquid separation step are immersed in a washing solution that is 10 times or less, preferably 1 to 9 times, more preferably 1.7 to 8 times, and even more preferably 1.5 to 7 times the volume of the polymer particles, and then the washing process is carried out, and if necessary, the polymer particles on the filter medium after washing are again immersed in a washing solution that is 10 times or less, preferably 1 to 9 times, more preferably 1.7 to 8 times, and even more preferably 1.5 to 7 times the volume of the polymer particles, and the washing process is repeated.And, it has been found that the amount of surfactant present in the polymer particles can be controlled by immersing the cake of polymer particles in the washing solution.

[0074] For example, in the cleaning process, when a pressure filter is used that includes a pressure vessel having a cylindrical internal space, a filter medium placed on the inner bottom of the pressure vessel, and a compressed gas supplying device that supplies compressed gas into the pressure vessel, the cake of polymer particles remaining on the filter medium is brought into contact with the cleaning liquid by supplying the cleaning liquid into the pressure vessel while the cake is still held on the filter medium. At this time, the cake is immersed in the cleaning liquid, and the cake is liquefied, thereby self-repairing the cracks in the cake. This eliminates the short pass of the cleaning liquid, reduces the amount of cleaning liquid used, and enables efficient cleaning.

[0075] Next, compressed gas is supplied to the space above the filter medium in the pressure vessel by the compressed gas supply machine to pressurize the space above the filter medium, whereby the cake comes into contact with the washing liquid and is washed, and the washing liquid after washing is discharged outside the pressure vessel as filtrate. In the washing step, after a washing liquid is introduced into the filter and brought into contact with the polymer particles, the washing liquid supplied into the filter and the cake may be mixed with a stirrer to form a slurry before pressurization. Before supplying the cleaning liquid for cleaning, the cake cracks may be repaired using a stirrer, which will prevent the cleaning liquid from short-passing, allowing for efficient cleaning.

[0076] In the washing process, the pressure conditions when the space above the filter medium in the pressure vessel is pressurized using a pressure filter are not particularly limited. For example, it is preferable to pressurize the pressure vessel so that the internal pressure is within the range of 0.01 to 0.50 MPa. In addition, it is preferable to pressurize the space above the filter medium at a speed of 0.01 to 0.30 MPa / min. In addition, in the washing process, it is preferable that the internal pressure of the pressure vessel is kept almost constant from the start of pressurization to the end of the washing process. In addition, the internal pressure of the pressure vessel gradually decreases after pressurization as the introduced washing liquid passes through the filter medium. Specifically, when the amount of washing liquid passing through the filter medium decreases or almost disappears, the compressed air pressure in the pressure vessel escapes from the bottom, making it difficult to maintain the internal pressure of the pressure vessel at the pressure when pressurized.

[0077] In the washing step, it is preferable to carry out the washing until 70% by mass or more, preferably 90 to 97% by mass of the medium passes through the filter material, based on 100% by mass of the medium contained in the crude product put into the filter (pressure filter) (when all the crude products obtained in the polymerization step are put into the filter material, the amount of the medium used in the polymerization step). This makes it possible to remove unnecessary components such as by-products (emulsion polymerization products) generated during the polymerization reaction, excess surfactants, polymer dispersion stabilizers used as needed, and additives such as polymerization inhibitors used as needed. This makes it possible to easily adjust (reduce) the amount of surfactants and non-volatile components contained in the polymer particles remaining on the filter material. In the cleaning process, if the amount of medium passing through the filter medium (discharge amount) is less than 70 mass% relative to 100 mass% of the amount of medium contained in the crude product, it may not be possible to sufficiently remove unnecessary components, and it may be difficult to adjust (reduce) the amount of surfactant and non-volatile components contained in the polymer particles remaining on the filter medium.

[0078] In the washing step, when a pressure filter is used as a filter, it is preferable to end the washing step when 70% or more by mass of the medium contained in the crude product that is put into the pressure filter passes through the filter medium and the internal pressure of the pressure vessel becomes 2 / 3 or less of the pressure when pressurized.This can reliably reduce the amount of unnecessary components remaining in the polymer particles that remain on the filter medium.

[0079] The washing liquid used in the washing step is preferably an aqueous medium, for example, water, lower alcohols having 5 or less carbon atoms such as methyl alcohol and ethyl alcohol, mixtures thereof, etc. In particular, it is preferable to use the same medium as that used in the polymerization step. The mass of the washing liquid used in the washing step is preferably 10 times or less, preferably 1 to 9 times, more preferably 1.7 to 8 times, and even more preferably 1.5 to 7 times, of the mass of the polymer particles held on the filter medium (when all the crude products obtained in the polymerization step are put into the filter in the solid-liquid separation step, the total amount of the vinyl monomers used in the polymerization step). In the present invention, by immersing the cake of the polymer particles held on the filter medium in the washing liquid, the cake is liquefied and the cracks in the cake are self-repaired. Therefore, there is no short pass of the washing liquid, and efficient washing can be performed, and there is no need to use a large amount of washing liquid. By using a washing liquid with a mass of 10 times or less, it is possible to prevent the surfactant and non-volatile components from being eluted more than necessary in the washing step, and the amount of the surfactant and non-volatile components contained in the polymer particles can be easily controlled.

[0080] The mass of the washing liquid used in the washing step can be adjusted to an appropriate amount in consideration of the type of each surfactant used in the polymerization step, etc., to further reduce the content of each component attached to the surface of the polymer particles. For example, if the amount of the washing liquid exceeds an appropriate amount, the surfactant having an SP value of 9.0 to 12.0 and a polyoxyalkylene chain is gradually eluted, and the amount of the surfactant having an SP value of 9.0 to 12.0 and a polyoxyalkylene chain contained in the polymer particles may not be the specified amount.

[0081] In the washing step, the filtration rate for removing the washing liquid from the polymer particles is not particularly limited. For example, the filtration rate is 0.025 to 0.095 kg / min m 2 , preferably 0.025 to 0.08 kg / min m 2 , more preferably 0.028 to 0.075 kg / min m 2 The range may be: If the drainage rate is too fast, it may not be possible to sufficiently remove unnecessary components contained in the polymer particles, and it may become difficult to adjust (reduce) the amount of surfactant and non-volatile components contained in the polymer particles. If the drainage rate is too slow, the solid-liquid separation step will take a long time, resulting in poor workability and the surfactant contained in the polymer particles may be lost more than necessary.

[0082] The temperature of the washing liquid used for washing is a temperature at which the surfactant used during polymerization is sufficiently eluted, for example, 40 to 80° C., preferably 50 to 80° C. As a method for heating the washing liquid to a temperature for washing, a method of supplying the heated washing liquid to the filter may be used, or a method of supplying the washing liquid to the filter and then heating the washing liquid by a heater jacket disposed around the filter may be used.

[0083] The washing process is preferably terminated when the conductivity of the washing liquid that has passed through the filter medium becomes 2.0 times or less the conductivity of the washing liquid before it was introduced into the filter (pressure filter) and the internal pressure of the pressure-resistant vessel becomes 2 / 3 or less of the pressure during pressurization. By washing until the conductivity of the washing liquid that has passed through the filter medium becomes 2.0 times or less, the amount of unnecessary components remaining in the polymer particles finally obtained can be reliably reduced. In addition, by washing until the internal pressure of the pressure-resistant container becomes 2 / 3 or less of the pressure at the time of pressurization, the amount of water that can be absorbed by the polymer particles can be reduced, and the time required for drying the polymer particles after washing can be shortened.

[0084] <Drying process and classification process> The polymer particles obtained in the washing step are preferably dried in a known dryer to remove the washing liquid. The dryer is not particularly limited, but it is preferable to use a vacuum dryer, for example, a vacuum stirring dryer (disintegrating dryer) equipped with stirring blades. The washing liquid is almost completely removed by drying, and the polymer particles can be made usable as a product by classifying (preferably air classification) as necessary.

[0085] The drying conditions in the present invention are appropriately adjusted depending on the capacity and performance of the dryer used, and for example, the following conditions can be adopted. The degree of vacuum (relative to atmospheric pressure) can be, for example, in the range of -0.001 to -0.5 MPa, and preferably in the range of -0.05 to -0.1 MPa. The drying temperature can be, for example, in the range of 40 to 80°C, preferably 50 to 70°C. The drying time can be, for example, 4 to 10 hours (hr), and preferably 7 to 9 hours. The operating conditions of the dryer used can be such that the stirring share coefficient calculated by the following formula (4) is in the range of 1800 to 2800, preferably 1900 to 2800, and more preferably 1950 to 2750. Mixing share coefficient = [total area of ​​mixing blades (m 2 ) × rotation speed (rpm) × time (hr)] / [amount of polymer particles (kg) × bulk density of polymer particles (unitless)] (4) (Bulk density measurements are based on JIS Z 8807:2012) If the stirring shear coefficient value is greater than 2800, the stirring force acting on the resin becomes too large, which may result in the particles being broken. If the stirring shear coefficient value is less than 1800, the stirring force acting on the resin will be too small, and the non-volatile components will not be sufficiently separated from the particles by shear, which may result in an unnecessarily large amount remaining. The amount of polymer particles to be charged into the dryer may be in the range of 0.1 to 1000 kg, preferably 0.5 to 500 kg.

[0086] In the present invention, in the drying step, the surfactant is dissolved from the polymer particle surface into water, and then a disintegrating dryer is used to scrape off the non-volatile components together with the water from the particle surface by the action of stirring shear, and then the non-volatile components are separated by suction. This makes it possible to adjust the surfactant content per unit surface area of ​​the polymer particle and the amount of surface residue of the non-volatile components on the polymer particle.

[0087] By pre-warming the washed cake, it becomes possible to easily adjust the surfactant on the particle surface to a specified amount. Furthermore, the non-volatile components are sheared by the crushing and drying process, and most of them are separated. The surfactant effectively modifies the polymer particle surface, resulting in polymer particles with excellent dispersion uniformity and improved dispersibility.

[0088] According to such a method for producing polymer particles, the surfactant attached to the polymer particles in the polymerization step can be appropriately removed together with the medium and the washing liquid. Furthermore, when a vinyl monomer is polymerized in the presence of a surfactant having an SP value of 9.0 to 12.0 and a polyoxyalkylene chain, a surfactant having an SP value of 9.0 to 12.0 and no polyoxyalkylene chain, and a surfactant containing other surfactants, most of the other surfactants can be sufficiently removed together with the medium and the washing liquid. As a result, the content (residual amount) of the surfactant having an SP value of 9.0 to 12.0 and a polyoxyalkylene chain and the surfactant having an SP value of 9.0 to 12.0 and no polyoxyalkylene chain per unit surface area of ​​the polymer particles can be appropriately adjusted, and the content (residual amount) of the other surfactants can be extremely reduced, and further, the content (residual amount) of the non-volatile components can also be appropriately adjusted.

[0089] [Applications of polymer particles] The polymer particles of the present invention can be used for various purposes, for example, as optical members, paint additives, and antiblocking agents. For example, a resin composition containing polymer particles and a resin binder can be formed, and this can be used to obtain optical films such as antiglare films and light diffusion films, optical members such as light diffusers, and in particular antiglare members. For example, a coating material can be obtained from the polymer particles themselves or from a mixture of the polymer particles with a binder resin, additives, and the like. For example, the polymer particles themselves or a mixture of the polymer particles and a resin can be molded to obtain a resin molded product. For example, the polymer particles themselves can be mixed with a resin as an antiblocking agent to form a resin composition, which can then be used to form a resin molded product such as a film.

[0090] [Resin composition] The resin composition of the present invention contains the above-mentioned polymer particles of the present invention and a resin binder.

[0091] <Binder> The binder is not particularly limited and is appropriately selected depending on the required properties such as transparency, polymer particle dispersibility, light resistance, moisture resistance, and heat resistance. Examples of the resin binder include one or more types selected from the group consisting of (meth)acrylic resins, (meth)acrylic-urethane resins, urethane resins, polyvinyl chloride resins, polyvinylidene chloride resins, melamine resins, styrene resins, alkyd resins, phenolic resins, epoxy resins, polyester resins, silicone resins such as polysiloxane resins, modified silicone resins such as (meth)acrylic-silicone resins, silicone-alkyd resins, silicone-urethane resins, and silicone-polyester resins, fluorine-based resins such as polyvinylidene fluoride and fluoroolefin vinyl ether polymers, and the like.

[0092] From the viewpoint of improving the durability of the resin composition, the resin binder is preferably a curable resin capable of forming a crosslinked structure by a crosslinking reaction. The curable resin can be cured under various curing conditions, and can be a thermosetting resin, a photocurable resin, an ultraviolet curable resin, an ionizing radiation curable resin such as an electron beam curable resin, or a warm air curable resin. The thermosetting resin may be at least one selected from the group consisting of a thermosetting urethane resin made of an acrylic polyol and an isocyanate prepolymer, a phenol resin, a urea melamine resin, an epoxy resin, an unsaturated polyester resin, a silicone resin, and the like.

[0093] The ionizing radiation curable resin may include one or more resins selected from the group consisting of polyfunctional (meth)acrylate resins such as polyhydric alcohol polyfunctional (meth)acrylates; and polyfunctional urethane acrylate resins synthesized from diisocyanates, polyhydric alcohols, and (meth)acrylic acid esters having hydroxyl groups. The ionizing radiation curable resin is preferably one containing a polyfunctional (meth)acrylate resin, more preferably one containing a polyhydric alcohol polyfunctional (meth)acrylate having three or more (meth)acryloyl groups in one molecule. Examples of polyhydric alcohol polyfunctional (meth)acrylates having three or more (meth)acryloyl groups in one molecule include one or more selected from the group consisting of trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tri(meth)acrylate, pentaglycerol triacrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol triacrylate, and tripentaerythritol hexaacrylate.

[0094] In addition to these, the ionizing radiation curable resin may be one or more resins selected from the group consisting of polyether resins having acrylate functional groups, polyester resins, epoxy resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, and the like. The resin binder may contain a thermoplastic resin in addition to the curable resin. The thermoplastic resin may be one or more selected from the group consisting of cellulose derivatives such as acetyl cellulose, nitrocellulose, acetyl butyl cellulose, ethyl cellulose, and methyl cellulose, vinyl resins such as homopolymers and copolymers of vinyl acetate, homopolymers and copolymers of vinyl chloride, and homopolymers and copolymers of vinylidene chloride, acetal resins such as polyvinyl formal and polyvinyl butyral, (meth)acrylic resins such as homopolymers and copolymers of acrylic acid esters, and homopolymers and copolymers of methacrylic acid esters, polystyrene resins, polyamide resins, linear polyester resins, and polycarbonate resins.

[0095] The resin binder may be a rubber-based binder such as synthetic rubber or natural rubber, or an inorganic binder, etc. The rubber-based binder resin may be one or more selected from the group consisting of ethylene-propylene copolymer rubber, polybutadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, etc. The inorganic binder may be one or more selected from the group consisting of silica sol, alkali silicate, silicon alkoxide, phosphate, etc. The inorganic binder may be an inorganic or organic-inorganic composite matrix obtained by hydrolysis and dehydration condensation of metal alkoxide or silicon alkoxide. The inorganic or organic-inorganic composite matrix may be a silicon oxide matrix obtained by hydrolysis and dehydration condensation of silicon alkoxide, such as tetraethoxysilane.

[0096] The amount of the polymer particles in the resin composition is 2 parts by mass or more, preferably 4 parts by mass or more, and more preferably 6 parts by mass or more, based on 100 parts by mass of the solid content of the resin binder. By making the amount of the polymer particles 2 parts by mass or more, the layer (coating film) formed by the resin composition can fully exhibit optical properties such as matte finish, and thus the optical properties such as antiglare property and light diffusion property of the optical member formed by coating the resin composition on a substrate can be made sufficient. The amount of the polymer particles in the resin composition is 300 parts by mass or less, preferably 200 parts by mass or less, more preferably 100 parts by mass or less, based on 100 parts by mass of the solid content of the binder. By making the amount 300 parts by mass or less, it becomes easier to make the linear permeability of the coating film formed by the coating resin composition sufficient.

[0097] When a photocurable resin or an ultraviolet ray curable resin is used among the ionizing radiation curable resins, a photopolymerization initiator can be added to the resin binder. Any photopolymerization initiator may be used, but it is preferable to use one that is suitable for the photocurable resin or ultraviolet curable resin used. As the photopolymerization initiator, for example, one or more types selected from the group consisting of acetophenones, benzoins, benzophenones, phosphine oxides, ketals, α-hydroxyalkylphenones, α-aminoalkylphenones, anthraquinones, thioxanthones, azo compounds, peroxides, 2,3-dialkyldione compounds, disulfide compounds, fluoroamine compounds, aromatic sulfonium compounds, onium salts, borate salts, active halogen compounds, α-acyloxime esters, and the like can be used. The amount of the photopolymerization initiator used is usually within a range of 0.5 to 20% by mass, and preferably within a range of 1 to 5% by mass, based on 100% by mass of the binder.

[0098] The resin composition may contain an organic solvent as necessary. In particular, when the resin composition is to be applied to a substrate, the application can be easily performed by including an organic solvent. Examples of the organic solvent include aromatic solvents such as toluene and xylene, alcohol solvents such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and propylene glycol monomethyl ether, ester solvents such as ethyl acetate and butyl acetate, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone, 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, and propylene glycol monomethyl ether. One or more solvents selected from the group consisting of glycol ethers such as pyrene glycol methyl ether, glycol ether esters such as 2-methoxyethyl acetate, 2-ethoxyethyl acetate (ethyl cellosolve acetate), 2-butoxyethyl acetate, propylene glycol methyl ether acetate, and the like, chlorine-based solvents such as chloroform, dichloromethane, trichloromethane, methylene chloride, and the like, ether-based solvents such as tetrahydrofuran, diethyl ether, 1,4-dioxane, 1,3-dioxolane, and the like, and amide-based solvents such as N-methylpyrrolidone, dimethylformamide, dimethylsulfoxide, dimethylacetamide, and the like can be used.

[0099] In the resin composition of the present invention, the dispersibility (compatibility) of the polymer particles is correlated with the viscosity value. The polymer particles of the present invention have a content of a surfactant having a polyoxyalkylene chain with an SP value of 9.0 to 12.0 of 1.0×10 per unit surface area of ​​the polymer particles. -3 ~6.0×10 -3 g / m 2 and the amount of a surfactant having an SP value of 9.0 to 12.0 and no polyoxyalkylene chain is 5.0 × 10 -5 ~13.0×10 -5 g / m 2 The amount of non-volatile residue on the surface is 2.0×10-3 g / m 2 The following is the result. Therefore, when the change in viscosity over time was measured using an ultra-small sample viscometer (manufactured by Rheosens, "m-VROC"), the dispersibility in the resin composition was (1) As the particles become soluble in the solvent, they disperse uniformly, increasing the viscosity value and reaching a maximum peak (value A) at a certain point. (2) As the compatibility stabilizes, the dispersion region narrows again and the viscosity value decreases. (3) After a certain period of time, the viscosity stabilizes at a certain stable value (B value). A series of viscosity changes occurs over time, resulting in excellent dispersion stability in the resin composition. In the present invention, the maximum peak value of the viscosity (A value), the stable value of the viscosity (B value), and the time h (hr) until the viscosity stabilizes are determined by the following formulas (5) and (6): A×0.1≦B≦A×0.5 (5) h<12 (6) It has been found that when both of the above conditions are satisfied, the dispersion stability in the resin composition is good, and when the resin composition is coated to produce an optical component, the component exhibits uniform optical properties (excellent dispersion uniformity). In equation (5), if the B value is smaller than the appropriate range, the viscosity is low and the particles aggregate, and if the B value is larger than the appropriate range, the viscosity is too high and the surfactants aggregate, slowing down the movement of the particles.

[0100] The above A value, B value and h value were specifically obtained by the following measurement methods. -Equipment used- Ultra-micro sample viscometer (manufactured by Rheosens, "m-VROC") -procedure- (i) 0.50 g of polymer particles are placed in a 50 cc sample bottle, and 5.0 g of toluene is added. Then, the mixture is dispersed for 5 minutes using an ultrasonic cleaner. (ii) 0.3 g of an acrylic resin (manufactured by DIC Corporation, "Acrydic (registered trademark) A-814") is added, and then the mixture is dispersed for 5 minutes using an ultrasonic cleaner to prepare a sample. (iii) The viscosity of the prepared sample is measured at 10 minute intervals until the rate of change in viscosity is less than 3%. Among the measured viscosities, the maximum peak value is taken as value A. The viscosity value when the rate of change in viscosity becomes less than 3% and the viscosity stabilizes (stable value) is taken as value B. The time it takes for the viscosity to stabilize is defined as h.

[0101] [Optical components] The optical member of the present invention has a layer of the resin composition on a substrate. In the present invention, the resin composition containing the polymer particles of the present invention and a resin binder can be applied onto a substrate to form a layer of the resin composition. Examples of the optical member include a light diffusing film or an antiglare film for light diffusing or antiglare purposes.

[0102] The substrate is preferably transparent. Examples of the transparent substrate include glass, polyester polymers such as polyethylene terephthalate (PET) and polyethylene naphthalate, cellulose polymers such as diacetyl cellulose and triacetyl cellulose (TAC), polycarbonate polymers, (meth)acrylic polymers such as polymethyl methacrylate, styrene polymers such as polystyrene and acrylonitrile-styrene copolymers, polyethylene, polypropylene, polyolefins having a cyclic or norbornene structure, olefin polymers such as ethylene-propylene copolymers, vinyl chloride polymers, amide polymers such as nylon and aromatic polyamides, polyimide polymers, polysulfone polymers, polyethersulfone polymers, polyetheretherketone polymers, polyphenylsulfide polymers, vinyl alcohol polymers, vinylidene chloride polymers, vinyl butyral polymers, arylate polymers, polyoxymethylene polymers, epoxy polymers, mixtures containing at least one of these polymers, and laminates of these polymers. Among these, those with a particularly low birefringence are preferably used. Furthermore, the substrate may have an easy-adhesion layer of a (meth)acrylic resin, a copolymer polyester resin, a polyurethane resin, a styrene-maleic acid grafted polyester resin, an acrylic grafted polyester resin, or the like provided on at least one surface thereof. The thickness of the substrate can be appropriately determined, but is generally within the range of 10 to 500 μm in terms of strength, workability such as handling, thinness, etc. It is preferably 20 to 300 μm, and more preferably 30 to 200 μm. The substrate may contain additives, such as ultraviolet absorbing agents, infrared absorbing agents, antistatic agents, refractive index adjusting agents, and enhancing agents. The method for applying the resin composition to the substrate is not particularly limited. For example, known coating methods such as bar coating, blade coating, spin coating, reverse coating, die coating, spray coating, roll coating, gravure coating, microgravure coating, lip coating, air knife coating, and dip coating can be used.

[0103] When the resin binder contained in the resin composition has ionizing radiation curing properties, the resin composition can be applied to a substrate to form a layer of the resin composition, and then the layer can be dried and cured by irradiating the substrate with active energy rays. Examples of the active energy rays that can be used include ultraviolet rays and infrared rays emitted from light sources such as LEDs, xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps; electron beams, α rays, β rays, γ rays, and the like, which are typically extracted from electron beam accelerators of 20 to 2000 KeV, such as Cockcroft-Walton type, Van de Graaff type, resonant transformer type, insulated core transformer type, linear type, dynamitron type, and high-frequency type. The thickness (dry thickness) of the layer of the resin composition is not particularly limited and is appropriately determined depending on the particle size of the polymer particles, and can be, for example, 1 to 10 μm, preferably 3 to 7 μm.

[0104] [Resin molding] The polymer particles of the present invention can be used alone or in combination with other resins to prepare resin molded articles by various molding methods. As the other resins, transparent resins can be preferably used, and in the resin molded articles, the polymer particles can function as light diffusing particles. The resin molded article functions as a light diffuser such as a light diffusion plate, and can be used as an LED lighting cover, etc.

[0105] The transparent resin may be, for example, one or more selected from the group consisting of (meth)acrylic resins, polycarbonate resins, polystyrene resins, (meth)acrylic-styrene resins (copolymers of (meth)acrylic acid esters and styrene), etc. Among these, polystyrene resins or (meth)acrylic-styrene resins are preferred.

[0106] When preparing a resin molded product from the polymer particles of the present invention and a transparent resin, the amount of the polymer particles contained in the resin molded product can be in the range of 0.01 to 5 parts by mass, preferably 0.1 to 5 parts by mass, per 100 parts by mass of the transparent resin. The resin molded product may contain additives such as ultraviolet absorbers, antioxidants, heat stabilizers, light stabilizers, and fluorescent whitening agents, as necessary. The thickness, shape, etc. of the resin molded body can be appropriately selected depending on the application.

[0107] The resin molded body can be obtained by melt-kneading the transparent resin and the polymer particles with a single-screw extruder, a twin-screw extruder, or the like. The resin composition obtained by melt-kneading may be molded into a plate shape through a T-die and a roll unit to obtain a resin molded body. The resin composition obtained by melt-kneading may be pelletized, and the pellets may be molded by injection molding, press molding, or the like to obtain a resin molded body. The resin molded article containing the polymer particles of the present invention has excellent dispersion uniformity of the polymer particles, and exhibits optical properties such as uniform light diffusibility and antiglare properties. EXAMPLES

[0108] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, "%" means "% by mass" and "parts" means parts by mass. Various measurement methods in the examples and comparative examples are as follows.

[0109] [Volume average particle size and standard deviation of particle size distribution of polymer particles] The volume average particle size and standard deviation of the particle size distribution of the polymer particles were measured using a Coulter Multisizer(TM)3 (manufactured by Beckman Coulter, Inc.) with an aperture calibrated according to the Multisizer(TM)3 User's Manual published by Beckman Coulter, Inc. The aperture used in the measurement is appropriately selected depending on the size of the polymer particles to be measured. Current (aperture current) and Gain are appropriately set depending on the size of the selected aperture. For example, when an aperture having a size of 50 μm is selected, Current (aperture current) is set to −800 and Gain is set to 4.

[0110] The measurement sample used is a dispersion obtained by dispersing 0.1 g of polymer particles in 10 ml of a 0.1% by mass aqueous solution of a nonionic surfactant using a touch mixer (manufactured by Yamato Scientific Co., Ltd., "TOUCHMIXER MT-31") and an ultrasonic cleaner (manufactured by Velvoclear Co., Ltd., "ULTRASONIC CLEANER VS-150") During the measurement, the contents of the beaker are gently stirred so as not to introduce air bubbles, and the measurement is terminated when 100,000 polymer particles have been measured. The volume average particle size of the polymer particles is the arithmetic average in a volume-based particle size distribution of 100,000 particles.

[0111] [Coefficient of variation of particle size (CV value)] The coefficient of variation (CV value) of the particle size of the polymer particles is calculated by the following formula. Coefficient of variation of particle size of polymer particles (CV value) = (Standard deviation of volume-based particle size distribution of polymer particles ÷ Volume average particle size of polymer particles) × 100

[0112] [Volume average particle size of seed particles] The volume average particle size of the seed particles used in the production of the polymer particles is measured using a laser diffraction / scattering type particle size distribution measuring device ("LS 13 320" manufactured by Beckman Coulter, Inc.) and a universal liquid sample module. The measurement sample used was a dispersion obtained by dispersing 0.1 g of a slurry containing seed particles in 10 ml of a 0.1% by mass aqueous solution of a nonionic surfactant using a touch mixer (manufactured by Yamato Scientific Co., Ltd., "TOUCHMIXER MT-31") and an ultrasonic cleaner (manufactured by Velvoclear Co., Ltd., "ULTRASONIC CLEANER VS-150")

[0113] The measurement is performed in a state where the seed particles are dispersed by pumping in the universal liquid sample module and the ultrasonic unit (ULM ULTRASONIC MODULE) is activated, and the volume average particle diameter of the seed particles (arithmetic mean diameter in the volume-based particle size distribution) is calculated. The measurement conditions are shown below.

[0114] Medium: water Refractive index of the medium: 1.333 Refractive index of solid: Refractive index of seed particles PIDS relative concentration: 40-55%

[0115] [Surfactant content in polymer particles] The content of the surfactant in the polymer particles is measured by extracting the polymer particles with a solvent and using a liquid chromatograph mass spectrometer (LC / MS / MS device). The LC / MS / MS devices used were "UHPLC ACCELA" manufactured by Thermo Fisher Scientific and "Linear Ion Trap LC / MSn LXQ" manufactured by Thermo Fisher Scientific.

[0116] The polymer particles of Examples 1 to 17 and Comparative Examples 1 to 10 contain, as a surfactant, a: POEPS: Phosphanol LO-529 (manufactured by Toho Chemical Industry Co., Ltd.) → Polyoxyethylene nonylphenyl ether sodium phosphate b: POSPS: Plysurf AL (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) → Polyoxyethylene styrenated phenyl ether phosphate ester c: POELE: Plysurf A210G (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) →Polyoxyethylene lauryl ether phosphate ester d: POEAS: Plysurf A208F (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) →Polyoxyethylene alkyl ether phosphate ester e:POEKG: Polyoxyethylene caprylic acid glyceryl f: POERS: Polyoxyethylene lauryl ether sodium phosphate g: POESM: Polyoxyethylene sorbitan monostearate i:DSS: Rapisol A-80 (NOF Corp.) → Sodium di(2-ethylhexyl)sulfosuccinate ii: ASK: Sodium alkenyl succinate iii: RSN: Sodium lauryl sulfate iv: PAI: isopropyl palmitate v:TOS: Sorbitan trioleate The surfactant content in the polymer particles in the examples and comparative examples was measured by the method described below.

[0117] Approximately 0.10 g of polymer particles as a sample is precisely weighed into a centrifuge tube, and 5 ml of methyl alcohol as an extraction solution is poured into the tube using a whole pipette to thoroughly mix the polymer particles with the extraction solution. After ultrasonic extraction at room temperature for 15 minutes, the mixture is centrifuged at 3500 rpm for 15 minutes, and the supernatant thus obtained is used as the test solution.

[0118] The surfactant concentration in this test solution is measured using an LC / MS / MS device. The surfactant content (μg / g) in the polymer particles is calculated from the measured surfactant concentration (μg / ml) in the test solution, the mass of the polymer particles used as the sample (sample mass (g)), and the amount of the extraction solution (amount of the extraction solution (ml)) according to the following formula. The amount of the extraction solution is 5 ml.

[0119] Surfactant content (μg / g) = {Concentration of surfactant in test solution (μg / ml) × Volume of extract (ml)} ÷ Mass of sample (g) The surfactant concentration is calculated from the peak area value on the obtained chromatogram using an LC / MS / MS device, using a calibration curve prepared in advance. When the polymer particles contain multiple types of surfactants, a calibration curve is prepared for each of the surfactants, and the surfactant concentration is calculated using the calibration curve. The total of the calculated surfactant concentrations of each surfactant is used as the "surfactant concentration (μg / ml) in the test solution" in the above formula to determine the surfactant content in the polymer particles.

[0120] The method for creating the calibration curve is as follows. <Calibration curve of surfactants having polyoxyethylene chains> For example, in the case of polyoxyethylene nonylphenyl ether phosphate, prepare an intermediate standard solution (methyl alcohol solution) of about 1000 ppm of polyoxyethylene nonylphenyl ether phosphate, and then further dilute it stepwise with methyl alcohol to prepare standard solutions for creating a calibration curve of 0.1 ppm, 0.5 ppm, 1.0 ppm, 2.0 ppm, and 10.0 ppm. The standard solutions for creating a calibration curve of each concentration are measured under the LC measurement conditions and MS measurement conditions described below, and the peak area value on the chromatogram of the monitor ion m / z = 502.3 (precursor ion) → 485.2 (product ion) is obtained. Each concentration and the area value are plotted to obtain an approximation curve (quadratic curve) by the least squares method, and this is used as the calibration curve for quantification. Calibration curves for other surfactants having a polyoxyethylene chain were prepared in a similar manner.

[0121] <Calibration Curve of Surfactants without Polyoxyethylene Chains> For example, in the case of di(2-ethylhexyl) sulfosuccinate, after preparing an intermediate standard solution of about 1000 ppm of di(2-ethylhexyl) sulfosuccinate (methyl alcohol solution), it is further diluted stepwise with methyl alcohol to prepare standard solutions for calibration curve of 0.1 ppm, 0.2 ppm, 0.5 ppm, 1.0 ppm, and 2.0 ppm. The standard solutions for calibration curve of each concentration are measured under the LC measurement conditions and MS measurement conditions described below, and the peak area values on the chromatogram of monitor ion m / z = 421.3 (precursor ion) → 227.2 (product ion) are obtained. The concentrations and area values are plotted and an approximate curve (quadratic curve) is obtained by the least squares method, which is used as the calibration curve for quantification. The calibration curves of other surfactants without polyoxyethylene chains were prepared in the same manner.

[0122] <LC Measurement Conditions> Measuring device: UHPLC ACCELA (manufactured by Thermo Fisher Scientific) Column: Hypersil GOLD C18 1.9μm (inner diameter 2.1 mm, length 100 mm) (manufactured by Thermo Fisher Scientific)

[0123] Measuring device: Linear Ion Trap LC / MSn LXQ (manufactured by Thermo Fisher Scientific) Ionization method (Ionization): (ESI / negative) Sheath Gas: 30 arb AUX Gas: 10 arb Sweep Gas: 0 arb I Spray Voltage: 5.0 kV Capillary Temp: 350 °C Capillary Voltage: -20 V Tube lens voltage: -100V Monitoring ion (m / Z): 200-2000

[0124] (Surfactants having polyoxyethylene chains) For example, in the case of polyoxyethylene nonylphenyl ether phosphate, it can be calculated from the monitor ions as (n=502.3 / n2=485.2). Similar calculations were performed for other surfactants having polyoxyethylene chains.

[0125] (Surfactants without polyoxyethylene chains) For example, in the case of di(2-ethylhexyl)sulfosuccinic acid, it can be calculated from the monitor ions as (n=421.3 / n2=227.2). The same calculations were carried out for other surfactants not having a polyoxyethylene chain.

[0126] [Specific surface area of ​​polymer particles] The specific surface area of ​​the polymer particles was measured by the BET method (nitrogen adsorption method) described in ISO 9277 1st Edition JIS Z 8830:2001. For the target polymer particles, the BET nitrogen adsorption isotherm was measured using an automatic specific surface area / pore distribution measuring device (Shimadzu Corporation, "Tristar3000"), and the specific surface area was calculated from the nitrogen adsorption amount using the BET multipoint method. The measurements were performed after pretreatment with heated gas purging, using nitrogen as the adsorbate, and the adsorbate cross section was 0.162 nm 2 The constant volume method was used under the conditions of: The pretreatment was specifically performed by purging with nitrogen for 20 minutes while heating a container containing the polymer particles at 65° C., allowing it to cool to room temperature, and then, while heating the container at 65° C., vacuum degassing was performed until the pressure inside the container reached 0.05 mmHg or less.

[0127] [Surfactant content (per unit surface area of ​​polymer particle)] Using the content of the surfactant in the polymer particles obtained above and the specific surface area of ​​the polymer particles obtained above, the content of the surfactant per unit surface area of ​​the polymer particles was calculated according to the following formula. The surfactant content per unit surface area of ​​the polymer particle (g / m 2 ) = (surfactant content in polymer particles (g / 1g of polymer particles) ÷ specific surface area of ​​polymer particles (m 2 / g)

[0128] [Amount of non-volatile residue on the surface (per unit surface area of ​​polymer particles)] <Quantitative analysis of non-volatile components> When polymer particles are dispersed in water and centrifuged, the polymer particles having the desired particle size settle, while the by-products (emulsion polymerization products) contained in the polymer particles float and form a supernatant together with a small amount of water. Therefore, the content of the by-products (emulsion polymerization products) in the polymer particles is measured here as the content of non-volatile components in the supernatant.

[0129] (Preparation of supernatant) 5.0 g of the polymer particles obtained in each Example and Comparative Example are placed in a sample bottle with a capacity of 50 ml, and 15.0 g of water is added. Then, the polymer particles are dispersed in water by performing a dispersion treatment for 60 minutes using an ultrasonic cleaner ("ULTRASONIC CLEANER VS-150" manufactured by Vervoclear Co., Ltd., oscillation frequency: 50 Hz, high frequency output: 150 W) to obtain a dispersion liquid. If the polymer particles are difficult to disperse in water, the polymer particles may be wetted with a small amount (up to 0.8 g) of alcohol (e.g., ethyl alcohol) and then dispersed in water. Next, 20.0 g of the dispersion is placed in a centrifuge tube with an inner diameter of 24 mm, for example, a centrifuge tube with a capacity of 50 ml and an inner diameter of 24 mm (manufactured by Thermo Fisher Scientific, product name "Nalgene (registered trademark) 3119-0050"), and the centrifuge tube is set in a rotor, for example, an angle rotor (model number "RR24A", manufactured by Hitachi Koki Co., Ltd., which holds eight centrifuge tubes with a capacity of 50 ml). The rotor is set in a centrifuge, for example, a high-speed refrigerated centrifuge (model number "CR22GII", manufactured by Hitachi Koki Co., Ltd.), and centrifuged using the high-speed refrigerated centrifuge under conditions of K factor 6943 (when the angle rotor is used, the K factor is 6943 at a rotation speed of 4800 rpm) and a rotation time of 30 minutes, and the supernatant is recovered.

[0130] (Quantitative Analysis of By-Products) The amount of by-products contained in the collected 5.0 g of supernatant was determined as follows: I asked. Weigh out 5.0 g of the supernatant into a 10 ml sample bottle whose mass has been measured in advance, and place it in a vacuum oven at 60°C for 5 hours to evaporate the water. Weigh the mass (g) of the sample bottle containing the evaporated residue, i.e., the non-volatile components. The concentration (mass%) of the non-volatile components (corresponding to by-products (emulsion polymerization products)) in the supernatant was calculated from the mass (g) of the sample bottle containing the non-volatile components, the mass (g) of the sample bottle, and the mass (g) of the supernatant placed in the sample bottle (=5.0 g) using the following formula. (Concentration of non-volatile components in the supernatant) (mass%) = {(mass of sample bottle containing non-volatile components) (g) - (mass of sample bottle) (g)} ÷ (mass of supernatant placed in sample bottle) (g) × 100

[0131] <Calculation of surface residue amount of non-volatile components (per unit surface area of ​​polymer particles)> Using the content of the non-volatile components in the polymer particles obtained above and the specific surface area of ​​the polymer particles, the amount of surface residue of the non-volatile components per unit surface area of ​​the polymer particles was calculated according to the following formula. The amount of non-volatile residue on the surface of polymer particles per unit surface area (g / m 2 ) = (content of non-volatile components in polymer particles (g / 1g of polymer particles) ÷ specific surface area of ​​polymer particles (m 2 / g)

[0132] [Gel fraction of polymer particles] The gel fraction of the polymer particles indicates the degree of crosslinking of the polymer particles, and is measured by the following method. 1.0 g of polymer particles as a sample and 0.03 g of boiling stones are precisely weighed and placed in a 200 ml recovery flask, and 100 ml of toluene is then added. A cooling tube is then attached to the recovery flask, which is then immersed in an oil bath maintained at 130°C and refluxed for 24 hours. After refluxing, the content (dissolved solution) in the eggplant flask is filtered using a Buchner funnel filter 3G (glass particle pore diameter 20 to 30 μm, volume 30 mL) manufactured by TOP Co., Ltd., which is equipped with glass fiber filters "GB-140 (φ37 mm)" and "GA-200 (φ37 mm)" manufactured by ADVANTEC Co., Ltd. and weighed, and the solid content is collected in the Buchner funnel filter 3G. The solid content collected in the Buchner funnel filter 3G is then dried together with the Buchner funnel filter 3G in a vacuum oven at 130° C. for 1 hour, and then dried at a gauge pressure of 0.06 MPa for 2 hours to remove the toluene, and cooled to room temperature. After cooling, the total mass of the Buchner funnel filter 3G, the glass fiber filter, and the solids is measured with the solids contained in the Buchner funnel filter 3G. The mass of the Buchner funnel filter 3G, the glass fiber filter, and the boiling stones is then subtracted from the measured total mass to determine the mass (g) of the dry powder. The gel fraction is calculated using the mass (g) of the dry powder and the mass (g) of the sample placed in the recovery flask according to the following formula. Gel fraction (mass%) = {dry powder (g) / sample mass (g)} x 100

[0133] [viscosity] (i) 0.50 g of polymer particles are placed in a 50 cc sample bottle, and 5.0 g of toluene is added. Then, the mixture is dispersed for 5 minutes using an ultrasonic cleaner. (ii) 0.3 g of an acrylic resin (manufactured by DIC Corporation, "Acrydic (registered trademark) A-814") is added, and then dispersed for 5 minutes using an ultrasonic cleaner. (iii) The viscosity was measured at 10-minute intervals using an ultra-micro sample viscometer (manufactured by Rheosens, "m-VROC") until the rate of change in viscosity became less than 3%. For each time period, the viscosity was measured by dispersing with ultrasonic waves for 1 minute, then leaving the mixture to stand for 10 minutes, after which the evaluation was performed.

[0134] [Dispersibility] (i) 0.1 g of polymer particles and 5 g of toluene were weighed into a plastic pot "A-4 (30)" and mixed using a degassing mixer (Thinky Corporation, Rotating / Revolving Mixer (Atmospheric Pressure Type) AR-100 (Product Name: THINKY MIXER (Non Vacuum) AR-100))) to prepare a sample. The mixing conditions were 3 minutes after mixing, 0 minutes of degassing, and 70 g of balance adjustment. (ii) After placing one drop of sample between a five-window type cover glass and a slide glass, it was observed and photographed using a digital microscope (Keyence Corporation, VHX-500). Two to three points were photographed at 700x magnification and evaluated according to the following criteria. Evaluation criteria: Uniformly dispersed throughout (aggregation rate less than 10%): A Dispersed throughout (aggregation rate is 10% or more but less than 30%): B Partial aggregation (aggregation rate is 30% or more but less than 70%): C The whole is aggregated (aggregation rate is 70% or more): D (A rating is the best in the evaluation criteria.)

[0135] [Time until uniform dispersion] (i) 0.50 g of polymer particles are placed in a 50 cc sample bottle, and 5.0 g of toluene is added. Then, the mixture is dispersed for 5 minutes using an ultrasonic cleaner. (ii) 0.3 g of an acrylic resin (manufactured by DIC Corporation, "Acrydic (registered trademark) A-814") is added, and then the mixture is dispersed for 5 minutes using an ultrasonic cleaner to prepare a sample. (iii) The viscosity of the prepared sample is measured at 10-minute intervals using an ultra-microsample viscometer (manufactured by Rheosens, "m-VROC") until the rate of change in viscosity becomes less than 3%. The time until the viscosity change rate becomes less than 3% and stabilizes is defined as the time until uniform dispersion.

[0136] [Optical properties] Using the polymer particles obtained in Examples 1 to 17 and Comparative Examples 1 to 10, resin compositions were prepared. The resin composition was applied to one side of a transparent polyester film so as to give a dry coating thickness of X μm, to prepare an optical film. The optical film was cut into a 6 cm x 6 cm square to prepare a test piece, and the haze of each of the four ends (top, bottom, left, right, and center) of the surface of the test piece coated with the coating resin composition (total of five locations) was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., "NDH-4000") in accordance with JIS K 7136. Then, using the maximum, minimum, and average values ​​of the haze (%) measured at the five locations, the haze difference (%) was calculated according to the following formula, and the haze difference (%) was evaluated according to the following evaluation criteria.

[0137] <Haze difference (%) formula> R = [(HzMAX-HzMIN) / HzAVE] x 100 R: Haze difference (%) HzMAX: Maximum haze value (%) of 5 points HzMIN: Minimum haze value (%) of 5 points HzAVE: Average haze value (%) of 5 points

[0138] <Evaluation criteria> A: Haze difference is less than 0.4% B: Haze difference is 0.4% or more and less than 1.0% C: Haze difference is 1.0% or more and less than 2.0% D: Haze difference is 2.0% or more (A rating is the best in the evaluation criteria.)

[0139] [Example of production of seed particles] [Seed particle production example 1] A separable flask equipped with a stirrer, a thermometer, and a reflux condenser was charged with 1300 g of water as an aqueous medium, 70 g of methyl methacrylate as a (meth)acrylic acid ester monomer, and 0.70 g of n-octyl mercaptan as a molecular weight regulator, and the inside of the separable flask was replaced with nitrogen while stirring the contents of the separable flask, and the internal temperature of the separable flask was raised to 70° C. Furthermore, while maintaining the internal temperature of the separable flask at 70° C., an aqueous solution in which 0.35 g of potassium persulfate was dissolved in 50 g of water as a polymerization initiator was added to the contents of the separable flask, and a polymerization reaction was carried out for 5 hours. Thereafter, 256 g of methyl methacrylate and 2.56 g of n-octyl mercaptan as a molecular weight regulator were newly charged and poured into the polymerization reaction liquid, after which the inside of the separable flask was replaced with nitrogen again and the internal temperature of the separable flask was raised to 70° C. While maintaining the internal temperature of the separable flask at 70° C., an aqueous solution in which 1.28 g of potassium persulfate was dissolved in 50 g of water as a polymerization initiator was added to the contents of the separable flask, and the polymerization reaction was carried out for 12 hours. The reaction liquid after polymerization was filtered through a wire screen of 400 mesh (openings 32 μm) to prepare a slurry containing 20 mass % of seed particles (referred to as seed particles (1)) made of polymethyl methacrylate as a solid content. The seed particles (1) contained in this slurry were spherical particles with a volume average particle diameter of 0.54 μm.

[0140] [Seed particle production example 2] A 5-liter reactor equipped with a stirrer and a thermometer was charged with 3300 g of water as an aqueous medium, 400 g of methyl methacrylate as a (meth)acrylic acid ester monomer, and 2.0 g of n-octyl mercaptan as a molecular weight regulator, and the slurry of seed particles (1) produced in Production Example 1 of Seed Particles was added so that the solid content (seed particles) was 40.0 g, and the inside of the reactor was replaced with nitrogen while stirring the contents, and the internal temperature of the reactor was raised to 70° C. Further, while maintaining the internal temperature of the reactor at 70° C., an aqueous solution in which 2.0 g of potassium persulfate was dissolved in 60 g of water as a polymerization initiator was added to the contents in the reactor, and the polymerization reaction was carried out for 12 hours. The reaction liquid after polymerization was filtered through a wire screen of 400 mesh (opening 32 μm) to prepare a slurry containing 20 mass % of seed particles (hereinafter referred to as seed particles (2)) made of polymethyl methacrylate as a solid content. The seed particles (2) contained in this slurry were spherical particles with a volume average particle diameter of 1.02 μm.

[0141] [Seed particle production example 3] In a 5L reactor equipped with a stirrer and a thermometer, 3500g of water as an aqueous medium, 500g of methyl methacrylate as a (meth)acrylic acid ester monomer, and 5.0g of n-octyl mercaptan as a molecular weight modifier were charged, and the slurry of seed particles (1) produced in Production Example 1 of seed particles was added so that the solid content (seed particles) was 40.0g. The inside of the reactor was replaced with nitrogen while stirring the contents, and the internal temperature of the reactor was raised to 70°C. Furthermore, while maintaining the internal temperature of the reactor at 70°C, an aqueous solution in which 5.0g of 2,2'-azobis(2,4-dimethylvaleronitrile) as a polymerization initiator was dissolved in 60g of water was added to the contents in the reactor, and the polymerization reaction was carried out for 12 hours. Thereafter, the internal temperature of the reactor was raised to 70°C, and the reaction was carried out for 1 hour and 30 minutes. The reaction liquid after polymerization was filtered through a wire screen of 400 mesh (opening 32 μm) to prepare a slurry containing 20 mass % of seed particles (hereinafter referred to as seed particles (3)) made of polymethyl methacrylate as a solid content. The seed particles (3) contained in this slurry were spherical particles with a volume average particle diameter of 2.30 μm.

[0142] [Production of polymer particles: Example 1] (1) Polymerization process A monomer mixture was prepared by dissolving 300 g of methyl methacrylate (MMA), 200 g of styrene (St), 300 g of ethylene glycol methacrylate (EGDMA), and 9.7 g of 2,4-dimethylvaleronitrile (polymerization initiator). The monomer mixture was mixed with an aqueous surfactant solution prepared by adding 15 g of sodium di(2-ethylhexyl)sulfosuccinate (manufactured by NOF Corporation, product name "Rapisol (registered trademark) A-80", solubility in water at a liquid temperature of 25°C; 1.5 g / 100 ml; anionic surfactant (other surfactant) having no polyoxyalkylene chain) as a pure content to 900 g of ion-exchanged water, and the mixture was placed in a homomixer (manufactured by Primix Corporation, "TK homomixer MARK II 2.5 type") and treated at a rotation speed of 8000 rpm for 10 minutes to obtain an emulsion. The slurry of seed particles obtained in Production Example 1 of seed particles was added to this emulsion so that the solid content (seed particles) became 18.75 g, and the mixture was stirred at 30°C for 5 hours to obtain a dispersion. To this dispersion was added 2250 g of an aqueous solution in which 15 g of pure polyoxyethylene nonylphenyl ether sodium phosphate (manufactured by Toho Chemical Industry Co., Ltd., product name "Phosphanol (registered trademark) LO-529"; an anionic surfactant having a polyoxyalkylene chain) was dissolved, and the mixture was then stirred at 75°C for 4 hours and then at 100°C for 1.5 hours to carry out a polymerization reaction, thereby obtaining a slurry of polymer particles.

[0143] (2) Solid-liquid separation process The obtained slurry of polymer particles was put into the pressure vessel of the pressure filter, and the slurry of polymer particles was filled on the filter cloth in the pressure vessel. After that, the inside of the pressure vessel (the space above the filter medium) was pressurized by supplying compressed gas to the space above the filter medium in the pressure vessel by a compressed gas supplying machine. In this way, the slurry of polymer particles was subjected to pressure filtration and dehydration, and the aqueous medium (water) was removed from the slurry of polymer particles as filtrate. The dehydration rate was 0.061 [kg / min m 2 The deliquation was continued until 78% of the charged water was recovered as filtrate, thereby obtaining a cake of polymer particles on the filter medium.

[0144] (3) Cleaning process The filtrate inlet and filtrate outlet of the pressure filter were closed, and the cake of polymer particles was held on the filter medium, and water at 60°C was supplied as a washing liquid in an amount twice that of the polymer particles, and the filter medium was immersed for 1 hour. After that, compressed gas was supplied to the space above the filter medium in the pressure vessel by a compressed gas supplying machine, thereby pressurizing the inside of the pressure vessel (the space above the filter medium). This performed pressure filtration and dehydration, washing the cake of polymer particles, and removing the washing water as filtrate to obtain washed polymer particles on the filter medium. The filtration rate was set to 0.100 [kg / min m 2 ] and washing was continued until 95% of the washing solution was recovered at the filtrate outlet.

[0145] (4) Drying process The washed polymer particles obtained in the washing step were preheated to 60°C and dried using a vacuum dryer (vacuum agitation dryer (disintegrator dryer)) until the moisture content of the polymer particles measured by the Karl Fischer method became less than 1.0% by mass. The conditions for the drying process were a vacuum degree of −0.075 MPa, a drying temperature of 60°C, a drying time of 8 hours, and a stirring shear coefficient of 2323.

[0146] (5) Classification process (removal of coarse particles) The dried polymer particles obtained in the drying step were classified using an air classifier (Turbo Classifier (registered trademark) TC-15 manufactured by Nisshin Engineering Inc.) so as to remove particles having a particle diameter 2.5 times or more the particle diameter of the target polymer particles, thereby obtaining the target polymer particles.

[0147] [Production of polymer particles: Example 2] As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 10 g of sodium alkenyl succinate was used in pure form. In the drying process, the vacuum degree was set to -0.100 MPa and the stirring shear coefficient was set to 2441. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0148] [Production of polymer particles: Example 3] The solid-liquid separation step was carried out until 79% of the charged water was recovered as a filtrate. In the drying process, the vacuum degree was set to -0.050 MPa and the stirring shear coefficient was set to 1983. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0149] [Production of polymer particles: Example 4] The monomer composition was 300 g of methyl methacrylate (MMA), 200 g of styrene (St), 300 g of ethylene glycol methacrylate (EGDMA), and 45 g of polyethylene glycol-propylene glycol-monomethacrylate. As an anionic surfactant having a polyoxyalkylene chain, 15 g of polyoxyethylene styrenated phenyl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure form. The solid-liquid separation step was carried out until 79% of the charged water was recovered as a filtrate. The washing procedure was repeated three times. In the drying process, the vacuum degree was set to -0.075 MPa and the stirring shear coefficient was set to 2475. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0150] [Production of polymer particles: Example 5] The monomer composition was 300 g of methyl methacrylate (MMA), 200 g of styrene (St), 300 g of ethylene glycol methacrylate (EGDMA), and 45 g of polyethylene glycol-propylene glycol-monomethacrylate. As an anionic surfactant having a polyoxyalkylene chain, 15 g of polyoxyethylene lauryl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf A210G") was used in a pure amount. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0151] [Production of polymer particles: Example 6] The monomer composition was 300 g of methyl methacrylate (MMA), 200 g of styrene (St), 300 g of ethylene glycol methacrylate (EGDMA), and 45 g of polyethylene glycol-propylene glycol-monomethacrylate. As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 25 g of sodium di(2-ethylhexyl)sulfosuccinate was used in a pure form. As an anionic surfactant having a polyoxyalkylene chain, 15 g of polyoxyethylene alkyl ether phosphate ester (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf A208F") was used in a pure amount. In the washing process, the filtration rate is set to 0.200 [kg / min m 2 ]. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0152] [Production of polymer particles: Example 7] The monomer composition was 900 g of styrene (St) and 108 g of divinylbenzene (DVB). As an anionic surfactant having a polyoxyalkylene chain, 15 g of polyoxyethylene styrenated phenyl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure amount. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0153] [Production of polymer particles: Example 8] As an anionic surfactant having a polyoxyalkylene chain, 35 g of polyoxyethylene styrenated phenyl ether phosphate ester (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure amount. In the solid-liquid separation process, the deliquescence rate was set to 0.070 [kg / min m 2] was continued until 80% of the feed water was recovered as filtrate. In the washing process, the filtration rate is set to 0.200 [kg / min m 2 ]. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0154] [Production of polymer particles: Example 9] In the solid-liquid separation process, the deliquation rate is set to 0.030 [kg / min m 2 ] was continued until 83% of the feed water was recovered as filtrate. In the washing process, the filtration rate is set to 0.035 [kg / min m 2 ]. In the drying process, the vacuum degree was set to -0.100 MPa and the stirring shear coefficient was set to 2056. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0155] [Production of polymer particles: Example 10] The slurry of seed particles was the slurry of seed particles (2) obtained in Seed Particle Production Example 2, and the amount of the slurry used was 6.3 g in terms of solid content (seed particles). The monomer composition was 560 g of methyl methacrylate (MMA) and 300 g of ethylene glycol methacrylate (EGDMA). As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 5 g of sodium di(2-ethylhexyl)sulfosuccinate was used in a pure form. In the washing process, the filtration rate was set to 0.085 [kg / min m 2 ]. In the drying process, the vacuum degree was set to -0.060 MPa and the stirring shear coefficient was set to 2030. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0156] [Production of polymer particles: Example 11] The slurry of seed particles (1) was replaced with the slurry of seed particles (3) obtained in Seed Particle Production Example 3, and the amount used was 4.7 g in terms of solid content (seed particles). The monomer composition was 560 g of methyl methacrylate (MMA) and 300 g of ethylene glycol methacrylate (EGDMA). As an anionic surfactant having a polyoxyalkylene chain, 20 g of polyoxyethylene styrenated phenyl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure amount. In the drying process, the vacuum degree was −0.060 MPa, the drying time was 9 hours, and the stirring shear coefficient was 2579. Except for the above, the same procedure as in Example 10 was repeated to obtain the target polymer particles.

[0157] [Production of polymer particles: Example 12] As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 15 g of sodium lauryl sulfate was used in pure form. In the drying process, the stirring shear coefficient was set to 2545. Except for the above, the same procedure as in Example 11 was carried out to obtain the target polymer particles.

[0158] [Production of polymer particles: Example 13] As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 15 g of sodium lauryl sulfate was used in pure form. As an anionic surfactant having a polyoxyalkylene chain, 13 g of pure polyoxyethylene lauryl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf A210G") was used. In the drying process, the stirring shear coefficient was set to 2709. Except for the above, the same procedure as in Example 11 was carried out to obtain the target polymer particles.

[0159] [Production of polymer particles: Example 14] As the anionic surfactant having a polyoxyalkylene chain, 15 g of polyoxyethylene glyceryl caprylate was used in pure form. In the drying process, the stirring shear coefficient was set to 2673. Except for the above, the same procedure as in Example 11 was carried out to obtain the target polymer particles.

[0160] [Production of polymer particles: Example 15] As an anionic surfactant having a polyoxyalkylene chain, 13 g of polyoxyethylene styrenated phenyl ether phosphate ester (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure amount. In the solid-liquid separation process, the deliquescence rate was set to 0.065 [kg / min m 2 ] was continued until 80% of the feed water was recovered as filtrate. In the washing process, the filtration rate is set to 0.150 [kg / min m 2 ]. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0161] [Production of polymer particles: Example 16] As an anionic surfactant having a polyoxyalkylene chain, 35 g of polyoxyethylene styrenated phenyl ether phosphate ester (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure amount. In the solid-liquid separation process, the deliquescence rate was set to 0.070 [kg / min m 2 ] was continued until 80% of the feed water was recovered as filtrate. In the washing step, water at 60° C. was supplied as a washing liquid in an amount twice the amount of the polymer particles, and the polymer particles were immersed for 0.5 hours. In the drying process, the stirring shear coefficient was set to 2376. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0162] [Production of polymer particles: Example 17] As an anionic surfactant having a polyoxyalkylene chain, 35 g of polyoxyethylene styrenated phenyl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used in a pure amount. In the solid-liquid separation process, the deliquescence rate was set to 0.055 [kg / min m 2 ] was continued until 80% of the feed water was recovered as filtrate. In the washing process, the polymer particles were soaked for 0.5 hours in 60°C water (2 times the amount of the polymer particles) and the filtration rate was 0.085 kg / min m 2 ]. In the drying process, the vacuum degree was set to -0.055 MPa and the stirring shear coefficient was set to 2344. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0163] [Production of polymer particles: Comparative Example 1] As an anionic surfactant having a polyoxyalkylene chain, 10 g of sodium polyoxyethylene nonylphenyl ether phosphate (manufactured by Toho Chemical Industry Co., Ltd., product name "Phosphanol (registered trademark) LO-529") was used in a pure amount. The washing step was repeated five times. In the drying process, the vacuum degree was set to -0.085 MPa and the stirring shear coefficient was set to 2620. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0164] [Production of polymer particles: Comparative Example 2] To the composition of Example 1, 45 g of the hydrophilic monomer polyethylene glycol-propylene glycol-monomethacrylate was added. In the solid-liquid separation process, the deliquescence rate is set to 0.100 [kg / min m 2 ] was continued until 80% of the feed water was recovered as filtrate. In the washing process, the filtration rate is set to 0.300 [kg / min m 2 ]. In the drying process, the stirring shear coefficient was set to 2553. Other than that, the same procedure as in Comparative Example 1 was carried out to obtain the target polymer particles.

[0165] [Production of polymer particles: Comparative Example 3] The monomer composition was 300 g of methyl methacrylate (MMA), 200 g of styrene (St), 300 g of ethylene glycol methacrylate (EGDMA), and 45 g of polyethylene glycol-propylene glycol-monomethacrylate. As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 35 g of sodium di(2-ethylhexyl)sulfosuccinate was used in a pure form. As an anionic surfactant having a polyoxyalkylene chain, 15 g of pure polyoxyethylene styrenated phenyl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0166] [Production of polymer particles: Comparative Example 4] In the solid-liquid separation process, the deliquescence rate is set to 0.020 [kg / min m 2 ]. In the drying process, the vacuum degree was set to -0.090 MPa and the stirring shear coefficient was set to 2620. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0167] [Production of polymer particles: Comparative Example 5] As an anionic surfactant having a polyoxyalkylene chain, 15 g of pure polyoxyethylene styrenated phenyl ether phosphate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Plysurf AL") was used. In the drying process, the vacuum degree was set to -0.020 MPa and the stirring shear coefficient was set to 1260. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0168] [Production of polymer particles: Comparative Example 6] As the anionic surfactant having a polyoxyalkylene chain, 15 g of sodium polyoxyethylene lauryl ether phosphate was used in a pure form. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0169] [Production of polymer particles: Comparative Example 7] As the anionic surfactant having a polyoxyalkylene chain, 15 g of polyoxyethylene sorbitan monostearate was used in terms of pure content. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0170] [Production of polymer particles: Comparative Example 8] As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 15 g of pure isopropyl palmitate was used. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0171] [Production of polymer particles: Comparative Example 9] As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 15 g of pure sorbitan trioleate was used. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0172] [Production of Polymer Particles: Comparative Example 10] As an anionic surfactant not having a polyoxyalkylene chain (another surfactant), 15 g of pure isopropyl palmitate was used. As the anionic surfactant having a polyoxyalkylene chain, 15 g of sodium polyoxyethylene lauryl ether phosphate was used in a pure form. In the drying process, the vacuum degree was set to -0.015 MPa and the stirring shear coefficient was set to 996. Except for the above, the same procedure as in Example 1 was carried out to obtain the target polymer particles.

[0173] For Examples 1 to 17 and Comparative Examples 1 to 10, the volume average particle size, CV value, gel fraction, specific surface area, type and SP value of each surfactant, amount of each surfactant per unit surface area of ​​the polymer particle, amount of non-volatile components per unit surface area of ​​the polymer particle, viscosity measurement results, dispersibility, time until uniform dispersion, and optical properties of the obtained polymer particles are shown in Tables 2 to 4.

[0174] [Table 2]

[0175] [Table 3]

[0176] [Table 4]

[0177] The symbols in Tables 2, 3 and 4 are as follows: a: POEPS: Phosphanol LO-529 (manufactured by Toho Chemical Industry Co., Ltd.) → Polyoxyethylene nonylphenyl ether sodium phosphate b: POSPS: Plysurf AL (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) → Polyoxyethylene styrenated phenyl ether phosphate ester c: POELE: Plysurf A210G (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) →Polyoxyethylene lauryl ether phosphate ester d: POEAS: Plysurf A208F (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) →Polyoxyethylene alkyl ether phosphate ester e:POEKG: Polyoxyethylene caprylic acid glyceryl f: POERS: Polyoxyethylene lauryl ether sodium phosphate g: POESM: Polyoxyethylene sorbitan monostearate

[0178] i:DSS: Rapisol A-80 (NOF Corp.) → Sodium di(2-ethylhexyl)sulfosuccinate ii: ASK: Sodium alkenyl succinate iii: RSN: Sodium lauryl sulfate iv: PAI: isopropyl palmitate v:TOS: Sorbitan trioleate

[0179] The present invention can be embodied in various other forms without departing from its spirit or main characteristics. Therefore, the above-described embodiments are merely illustrative in all respects and should not be interpreted as being limiting. The scope of the present invention is defined by the claims and is not limited to the text of the specification. Furthermore, all modifications and changes within the scope of the claims are within the scope of the present invention.

Claims

1. (a) The content of a surfactant having a solubility parameter (SP value) of 9.0 to 12.0 and having a polyoxyalkylene chain is 1.0×10 per unit surface area of ​​the polymer particle. -3 g / m 2 to 4.25×10 −3 g / m 2 , or 4.4×10 −3 g / m 2 to 6.0×10 -3 g / m 2 , (b) The content of a surfactant having a solubility parameter (SP value) of 9.0 to 12.0 and having no polyoxyalkylene chain is 5.0 × 10 per unit surface area of ​​the polymer particle. -5 g / m 2~13.0×10 -5 g / m 2 , (c) The amount of surface residue of non-volatile components per unit surface area of ​​the polymer particles is 0.90×10 −3 g / m 2 or more and 2.0×10 -3 g / m 2 below, The polymer particles are

2. 2. The polymer particles according to claim 1, having a volume average particle size of 1 to 20 μm and a coefficient of variation (CV value) of particle size of the polymer particles calculated by the following formula of 15% or less. Coefficient of variation of particle size of polymer particles (CV value)=(Standard deviation of volume-based particle size distribution of polymer particles÷Volume average particle size of polymer particles)×100

3. 3. The polymer particles according to claim 1, wherein the surfactant having a polyoxyalkylene chain and an SP value of 9.0 to 12.0 is a phosphate-based anionic surfactant.

4. 3. The polymer particles according to claim 1, which are composed of one or more polymers selected from the group consisting of (meth)acrylic polymers, styrene polymers, and (meth)acrylic-styrene copolymers.

5. The polymer particles according to claim 1 or 2, which are used for optical members.

6. The polymer particles according to claim 1 or 2, which are used as a paint additive.

7. The polymer particles according to claim 1 or 2, which are used as an antiblocking agent.

8. A resin composition comprising the polymer particles according to any one of claims 1 to 4 and a resin binder.

9. An optical member having a layer of the resin composition according to claim 8 on a substrate.

Citation Information

Patent Citations

  • Light-diffusing agent and method for producing light-diffusing agent and light-diffusing sheet

    JP2006233055A

  • Polymer particles, method for producing same, and use of same

    WO2016051814A1

  • Polymer particles and use thereof

    WO2017056529A1